Oxide ceramics and production method therefor

By employing ZnO and TiO as sintering aids and low-temperature synthesis, the challenges of phase transitions and grain boundary segregation in rare earth oxide and zirconia ceramics are overcome, resulting in high-density, transparent ceramics with improved optical properties.

JP2025002948APending Publication Date: 2025-01-09WORLD LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023103358
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Existing methods for synthesizing rare earth oxide ceramics and zirconia ceramics face challenges in achieving high density and optical quality due to phase transitions and grain boundary segregation issues, particularly at high temperatures, leading to poor optical properties and structural instability.

Method used

The use of specific amounts of ZnO and TiO as sintering aids, combined with controlled low-temperature synthesis through processes like HIP treatment, to create dense and transparent rare earth oxide ceramics and monoclinic zirconia ceramics, avoiding phase transitions and grain boundary segregation.

Benefits of technology

This approach results in ceramics with high relative densities and superior optical properties, enabling the production of transparent bodies that were previously difficult to achieve, such as those with cubic crystal structures like Tb2O3, Dy2O3, and Gd2O3, and denser monoclinic zirconia ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002948000012
    Figure 2025002948000012
  • Figure 2025002948000013
    Figure 2025002948000013
  • Figure 2025002948000014
    Figure 2025002948000014
Patent Text Reader

Abstract

To provide more finer ceramics in rare earth oxide ceramics or zirconia ceramics.SOLUTION: The present invention relates to the oxide ceramics comprising: (1) (1-1) cubic system oxide ceramics containing at least one kind of chemical element including an atomic number 21(Sc), an atomic number 39(Y), and a lanthanoid rare earth of atomic number 57(La) to 71(Lu) or (1-2) monoclinic system oxide ceramics containing zirconium; and (2) the oxide ceramics of the (1-1) or (1-2) containing (a) at least one kind of ZnO and Ti oxide with the total amount of 50 to 10000 weight ppm (when containing an atomic number 65(Tb) as the chemical element, the content of Ti oxide is less than 1000 weight ppm.) and (b) at least one kind of MgO, CaO, and SrO with the total amount of 0 to 0.3 weight%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel oxide ceramic and a method for producing the same. [Background technology]

[0002] Densifying oxide ceramics is extremely important in terms of improving the translucency and mechanical strength (wear resistance, etc.) of oxide ceramics, and thus various manufacturing methods have been proposed.

[0003] For example, a method for imparting transparency to rare earth oxides is known in which the target oxide is melted at a high temperature of about 2400°C or higher and solidified to obtain a single crystal. However, for example, rare earth oxides such as Y2O3 undergo a phase transition from orthorhombic to cubic at 2280°C, which is below the melting point of 2400°C, so even if single crystallization is successful, changes in the crystal structure and volume occur due to the phase transition, which causes distortion in the single crystal. For this reason, in the worst case, cracks or material collapse due to the distortion occur, making it virtually impossible to stably obtain transparent single crystals.

[0004] There is a method of synthesizing polycrystals by sintering at a temperature below the melting point of the above single crystals. With this method, dense and transparent rare earth oxide ceramics can be obtained, since oxides of Sc, Lu, Y, etc., which have particularly small ionic radii, have high orthorhombic to cubic phase transition temperatures. When synthesizing these rare earth oxide ceramics, sintering aids are usually used to prevent grain growth caused by the coalescence of rare earth oxide particles during the sintering process and to promote the elimination of residual pores.

[0005] Greskovic synthesized a transparent rare earth oxide ceramic by adding 10% ThO2 as a sintering aid to Y2O3 and sintering the material in a hydrogen atmosphere at 2170℃ for more than 30 hours (Non-Patent Document 1). This material has a transmittance of about 80%, but a large amount of inclusions called orange peel were detected, the scattering was large at several % / cm, and the material was in an optically non-uniform state, so there was a risk of extremely large birefringence. In addition, when coherent light such as laser light is incident, there is a risk of beam distortion.

[0006] Other methods of synthesizing rare earth oxide ceramics using sintering aids have been proposed. For example, J. Zhang et al. added ZrO2 as a sintering aid to Lu2O3, pre-sintered it at 1600°C, and then HIP-treated it at a temperature of 1700°C and a pressure of 196 MPa to obtain a transparent body (Non-Patent Document 2).

[0007] For example, Ikesue et al. have reported a method for obtaining transparent Y2O3 ceramics containing Nd as a laser-active element by adding a small amount of HfO2, pre-sintering at 1650°C, and then HIPing at 1700°C (Non-Patent Document 3).

[0008] In order to obtain a transparent Y2O3 sintered body, a method has been proposed in which a small amount of BeO is added and sintered at a high temperature of 2150°C or higher (Non-Patent Document 4).

[0009] In addition, J. Zhang et al. have proposed a method of adding a small amount of ZrO2 to prepare transparent Tb2O3-Lu2O3 ceramics and then subjecting it to HIP treatment (Non-Patent Document 6).

[0010] As these reports also show, the synthesis temperatures for transparent rare earth oxide ceramics up to now have been 1600°C or higher, including pre-sintering and high-pressure sintering, and are extremely high at around 2000°C or higher for atmospheric pressure sintering.

[0011] Here, the stable phase diagram of various rare earth ions with respect to ionic radius and temperature is shown in Figure 1. Oxides with small ionic radius have a wide stable region of cubic crystals, so they can be synthesized (sintered) at high temperatures. If sintering is performed at a high temperature exceeding the stable region of cubic crystals, the sintered body will become cubic → orthorhombic, and the phase transition from orthorhombic to cubic will be repeated during the cooling process, causing optical distortion (birefringence) or cracks in the material, and even if a transparent sintered body is obtained, it cannot be used as a practical optical material. From this perspective, Tb2O3 and Dy2O3 are expected to be promising Faraday elements because of their large Verdet constants, but their phase transition temperatures are low at about 1500 to 1600 °C, so it is difficult to even prepare high-density sintered bodies. Furthermore, since the phase transition temperatures of Gd2O3 and Eu2O3, which have large ionic radii, are around 1200°C and 1050°C, respectively, there is no technology to produce dense sintered bodies at temperatures lower than these temperatures, and there have been no successful reports.

[0012] Thus, even in the synthesis of polycrystalline rare earth oxide ceramics, it is difficult to prepare materials suitable for optical applications, particularly in the case of oxides with relatively low phase transition temperatures.

[0013] In addition, there are also problems caused by sintering aids. That is, even if sintering aids are added to remove residual pores, the removal effect is insufficient, causing Mie scattering, and the baseline transmittance is lower than the theoretical value. In addition, sintering aids such as ZrO2 are dissolved inside rare earth oxide particles, but some of them become inclusions and precipitate or segregate near grain boundaries. Inclusions are large in size, so they cause Mie scattering similar to residual pores, while grain boundary segregation causes Rayleigh scattering because the scatterer size is at the nano level.

[0014] For example, in the case of the transmittance of sintered bodies such as Sc2O3, Y2O3, and Lu2O3 produced by adding sintering aids such as ZrO2, even though most of the samples are only a few mm thick, (a) the baseline transmittance is lower than the theoretical transmittance, and (b) the transmittance decreases as the measurement wavelength becomes shorter.

[0015] Regarding (a) above, it is suggested that the effect of the sintering aid for densification is insufficient, and that structural defects (mainly residual pores) of a size equal to or larger than the measurement wavelength remain inside the material. On the other hand, regarding (b) above, it is theoretically reasonable to assume that typical Rayleigh scattering occurs because the transmittance depends on the wavelength, and it is presumed that the sintering aid is segregated near the grain boundaries. And when either or both of the above problems (a) and (b) occur, the material becomes transparent, but its application as a practical optical material becomes impossible or limited.

[0016] Incidentally, because the amounts of these sintering aids added are relatively small and have a gentle distribution near the grain boundaries, they are difficult to detect using TEM-EDS (Transmission Electron Microscopy - Energy Dispersive Spectroscopy), and therefore SIMS (Secondary Ion Nass Spectroscopy) analysis must be relied upon.

[0017] J. Zhang et al. have shown the transmission spectrum of a sample in which ZrO2 was used as a sintering aid in the synthesis of rare earth oxide ceramics, and in a sample about 5 mm thick, the transmittance decreases as the measurement wavelength becomes shorter. This means that the grain boundary segregation of ZrO2 causes Rayleigh scattering inside the material. Most materials that use ZrO2 as a sintering aid show this transmission spectrum pattern, and good quality optical materials have yet to be developed.

[0018] Ikesue et al. added a small amount of ZrO2 to prepare transparent Y2O3-Tb2O3 ceramics, and obtained a high-quality sintered body by pre-sintering and HIP processing at a temperature range of 1500-1700°C (Non-Patent Document 7). However, the temperature at which Tb2O3 is prepared, at which the Verdet constant is at its maximum, is 1500°C or higher, which is above the phase transition point, and is therefore thought to cause distortion inside the material. In addition, the microstructure of the obtained sintered body was observed by TEM-EDS, but it is difficult to detect the grain boundary segregation of Zr by TEM-EDS.

[0019] Regarding this, the inventor reproduced a material of the same composition and analyzed the grain boundaries by SIMS, and confirmed the presence of grain boundary segregation of Zr. This suggests the need for further fundamental technological improvements, since as long as sintering aids such as ZrO2 and HfO2 are used, the difference in refractive index within the grains at the grain boundaries causes light scattering (Rayleigh scattering), and grain boundary scattering cannot be avoided.

[0020] In order to avoid such grain boundary scattering caused by sintering aids, there is a method to synthesize high density rare earth oxide ceramics without adding sintering aids. However, even in this case, a sintering temperature of around 1600°C results in insufficient optical properties (thickness of around 1mm, transmittance of only around 30% or less in the visible range), so long sintering times at temperatures of 2000°C or higher are required. As a result, the optical properties of the obtained material are very poor, and in reality it is far from being at a practical level.

[0021] For example, there is a case where a special nano-sized powder was synthesized and low-temperature sintering was attempted to produce a transparent Y2O3 sintered body without adding sintering aids (Non-Patent Document 5). However, even with this sintered body, the transmittance in the visible to near-infrared range remains at about 10 to 0% even when the sample thickness is as thin as 1 mm. If no sintering aid is added, the grain growth of Y2O3 is promoted during sintering, and the grain growth and the movement speed of the residual pores do not match, so the pores are trapped inside the particles, causing significant scattering. Transition metal elements have a smaller ionic radius than Sc, Y, and lanthanide rare earth elements, and it has been thought that they do not form a solid solution even if they are used as a sintering aid (i.e., transition metal elements cannot be replaced by Sc, Y, or lanthanide rare earth elements), so there are no examples of producing high-quality transparent rare earth oxide ceramics with added transition metal elements.

[0022] Thus, in the conventional technology, in order to realize low-temperature synthesis, the particle size of the starting material is reduced, for example from microns to nanometers, and a design is made to reduce the substantial mass transfer between particles by the so-called size effect. However, when the particle size is reduced, the repulsive force between the particles becomes stronger, and due to the influence of the decrease in packing during molding, it is not possible to substantially lower the temperature.

[0023] In particular, rare earth oxides are difficult to sinter, and therefore it is difficult to increase density or make them transparent without a sintering aid. Therefore, the oxides of Sr, Zr, Hr, etc. mentioned above are used as sintering aids to increase density, but care is taken to ensure that these elements do not end up substituting for cations in the rare earth oxide and precipitating at grain boundaries. In other words, elements with similar ionic radii are selected because their different valences from the rare earth elements can promote mass transfer within the material and they are thought not to precipitate at grain boundaries.

[0024] However, as mentioned above, even if SrO is added, it is not possible to suppress grain growth when rare earth oxide ceramics are fired at high temperatures, and so the only ceramics that have been reported are those in which pores remain inside the particles and significant Mie scattering occurs.

[0025] Adding ZrO2 or HfO2 can prevent grain growth during high-temperature firing like Sr, so ceramics with higher transmittance than Sr can be synthesized. For example, looking at the phase diagram of the Y2O3-ZrO2 system, the solid solubility range of ZrO2 in Y2O3 is large, so in ceramic synthesis, it is generally believed that ZrO2 will be uniformly dissolved in Y2O3 particles. However, when analyzed using SIMS, Zr is segregated near the grain boundaries of individual Y2O3 particles that make up the Y2O3 ceramics to which ZrO2 has been added. Since the segregation state of Zr differs depending on the synthesis conditions, the transmission spectrum of the material also differs. Non-Patent Documents 6 and 7 are typical examples. When the same amount of Zr is added to a similar material, Non-Patent Document 6 shows a significant wavelength dependency of the transmittance (i.e., the transmittance decreases as the measurement wavelength becomes shorter, which is a state in which so-called typical Rayleigh scattering occurs), while Non-Patent Document 7 has optical quality with little grain boundary scattering. This is due to differences in the control technology for Zr segregation at grain boundaries, but no matter how much control is applied, Zr segregation cannot be avoided.

[0026] Until now, it has been difficult to consider transition metal elements as sintering aids for rare earth elements (except Sc) because the ionic radius of transition metal elements is different from that of rare earth elements. In fact, when oxides of atomic numbers 22 (Ti) to 29 (Cu) in the periodic table are added as sintering aids to rare earth oxide ceramics, an increase in density is observed, but coloring and grain boundary segregation occur.

[0027] On the other hand, zirconia (ZrO2) also needs to be densified to provide higher functionality. However, since zirconia undergoes a phase transition from monoclinic to tetragonal at around 950-1100°C, it is nearly impossible to obtain a dense sintered body. When the sintering temperature exceeds 1100°C, the volume change (volume expansion of 4%) associated with the phase transition not only causes cracks in the sintered body, but in many cases leads to collapse.

[0028] To address this issue, a method has been proposed in which the zirconia raw material is subjected to CIP (Cold Isostatic Press) at a high pressure of 510 MPa to forcibly increase the initial density (Non-Patent Document 8). However, it is extremely difficult to obtain a dense sintered body by sintering at around 1100°C, and thus far only very small samples (0.8 cm2) have been produced. 3 The best results are in examples where a relative density of about 90% is achieved at a sintering temperature of about 100°C (about 100°F). Another problem is that some of the zirconia sintered bodies contain crystal phases other than monoclinic. Since there are no examples of the synthesis of monoclinic zirconia ceramics with high sintering density, the physical properties of this material cannot be investigated in detail, and therefore no clear application methods for the material have been established at present.

[0029] When stabilizers such as Y2O3 are added to ZrO2, the crystal phase changes from monoclinic to tetragonal to cubic, and there is no longer any restriction on the sintering temperature. Tetragonal zirconia materials have applications in engineering materials with high strength and toughness, such as grinding balls and bearings with high wear resistance, while cubic zirconia materials are used as functional materials such as solid electrolytes in SOFCs (Solid Oxide Fuel Cells). These applications are possible because their synthesis itself has become possible and their physical properties have been elucidated.

[0030] In contrast, monoclinic zirconia is practically impossible to synthesize because the phase transition occurs at a relatively low temperature as mentioned above, and applications of this material have not yet been established. If it becomes possible to synthesize this material and progress is made in elucidating its physical properties, there is the possibility that new applications not present in the existing market will emerge.

[0031] Thus, conventional techniques have limitations in densifying oxide ceramics. For this reason, although there is a demand for high-quality polycrystalline rare earth oxide ceramics, particularly for optical applications, such materials have not yet been developed. For the same reason, monoclinic zirconia ceramics with higher density have not yet been developed. [Prior art documents] [Non-patent literature]

[0032] [Non-Patent Document 1] C. Greskovich, K. Woods, "Fabrication of Transparent ThO2-doped Y2O3", Ceramic Bulletin, 52 [5] 473-8 (1973). [Non-Patent Document 2] Edited By A. Ikesue, “Processing of Ceramics”, pp.46, Wiley (Am. Ceram. Soc. (ISBN: 9781119538707 (2021). [Non-Patent Document 3] A. Ikesue, K. Kamata, K. Yoshida, "Synthesis of Transparent Nd-doped HfO2-Y2O3 Ceramics using HIP", J. Am. Ceram. Soc., 79[2] 359-64 (1996). [Non-Patent Document 4] Takazo Toda, Iwao Matsuyama, "Effect of BeO on the Sintering of Transparent Y2O3", Powder and Powder Metallurgy, Vol. 35, No. 6, 486-91(1988). [Non-Patent Document 5] N. Saito, S. Matsuda, T. Ikegami, "Fabrication of Transparent Yittria Ceramics at Low Temperature using Carbonate-Derived Powder", J. Am. Ceram. Soc., 81 [8] 2023-28 (1998). [Non-Patent Document 6] J. Zhang, H. Chen, J. Wang, D. Wang, S. Wang, "Preparation of (Tb1-xLux)2O3 Transparent Ceramics by Solid Solution for Magneto-Opticadoi:10.3390 / mal Application", J. Eur. Ceram. Soc., 41, 2818- 25 (2021). [Non-Patent Document 7] A. Ikesue, YL Aung, S. Makikawa, A. Yahagi, "Total Performance of Magneto-Optical Ceramics with a Bixbyite Structure", Materials, 12,421; doi:10.3390 / ma1230421 (2019). [Non-Patent Document 8] J. Eichler, U. Eisele, J. Rodel, "Mechanical Properties of Monoclinic Zirconia", J. Am. Ceram. Soc., 87 [7] 1401- 03 (2004). Summary of the Invention [Problem to be solved by the invention]

[0033] Therefore, a main object of the present invention is to provide a denser rare earth oxide ceramic or zirconia ceramic, and in particular, to provide a rare earth oxide ceramic having superior optical properties. [Means for solving the problem]

[0034] As a result of extensive research into the problems of the prior art, the present inventors have discovered that the above-mentioned object can be achieved by an oxide ceramic having a specific composition and structure, thereby completing the present invention.

[0035] That is, the present invention relates to the following oxide ceramics and a method for producing the same. 1. (1) (1-1) Cubic oxide ceramics containing at least one element of the lanthanoid rare earths having atomic numbers 21 (Sc), 39 (Y), and 57 (La) to 71 (Lu), or (1-2) Monoclinic oxide ceramics containing zirconium, (2) The oxide ceramic of (1-1) or (1-2) is (a) At least one of ZnO and Ti oxide: 50 to 10,000 ppm by weight in total (however, when the element contains the atomic number 65 (Tb), the content of Ti oxide is less than 1,000 ppm by weight); and (b) At least one of MgO, CaO, and SrO: 0 to 0.3% by weight in total 1. An oxide ceramic comprising: 2. The oxide ceramic according to item 1, having a relative density of 98% or more. 3. The oxide ceramic according to item 1, having an average crystal grain size of 0.3 to 50 μm. 4. The oxide ceramic according to item 1, wherein a sample of the oxide ceramic (1-1) having a thickness of 2 mm has an optical loss of 5% / cm or less for a light beam having a wavelength of 1 μm in the thickness direction. 5. The oxide ceramic according to item 4, wherein a sample of the oxide ceramic (1-1) having a thickness of 2 mm has an extinction ratio of 25 dB or more in the thickness direction for a light beam having a wavelength of 1 μm. 6. An optical element comprising the oxide ceramic according to item 4 above. 7. The optical element according to item 4, which is used in an optical passive product or an optical active product. 8. A method for producing rare earth oxide ceramics, comprising: (1) A process for obtaining a mixture by wet-mixing, in an alcohol, a raw material including (a) a powder of a rare earth element-containing substance having an average primary particle size of 0.05 to 3 μm and (b) a compound containing at least one of Zn and Ti as a sintering aid; (2) forming the mixture or a dried product thereof into a green compact; (3) pre-sintering the green compact at a temperature of 900 to 1450°C to obtain a pre-sintered body having a relative density of 91 to 99.8%; and (4) A step of subjecting the pre-sintered body to HIP treatment at a temperature of 1000 to 1600°C and a pressure of 98 to 392 MPa. A method for producing rare earth oxide ceramics, comprising the steps of: 9. A method for producing zirconia ceramics, comprising: (1) A process for obtaining a mixture by wet-mixing, in an alcohol, a raw material including (a) a monoclinic zirconia powder having an average primary particle size of 0.02 to 0.2 μm and (b) a compound including at least one of Zn and Ti as a sintering aid; (2) forming the mixture or a dried product thereof into a green compact; and (3) A step of sintering the green compact at a temperature of 1000 to 1100°C to obtain a sintered compact with a relative density of 92 to 99.8%. A method for producing zirconia ceramics, comprising: Effect of the Invention

[0036] According to the present invention, it is possible to provide a denser oxide ceramic, and in particular, it is possible to provide a rare earth oxide ceramic that also has superior optical properties.

[0037] In the present invention, a specific amount of ZnO and / or Ti oxide is particularly contained as a sintering aid, so that rare earth oxide ceramics with extremely good optical quality can be provided because they are denser. Furthermore, it is also possible to provide high-density monoclinic zirconia ceramics, the detailed physical properties of which are unknown because the synthesis method has not been established. Moreover, synthesis can be performed at a low temperature range that is unthinkable with previous sintering aids. As a result, it is also possible to realize the production of transparent bodies of oxides of Dy, Tb, Gd, Eu, etc. with a cubic crystal structure, which have been extremely difficult to synthesize due to phase transition problems.

[0038] There have been no reports to date that oxides of transition metals such as Zn or Ti are effective in densifying or making transparent rare earth oxide ceramics. 2+ and Ti 4+ The ionic radii of Y, which is a representative rare earth ion, are 0.74 and 0.68 Å, respectively. 3+ and Lu 3+ Since the ionic radii of ZnO and TiO2 are smaller than those of ZnO and TiO2, respectively, it is believed that lattice substitution will be difficult. Therefore, even if ZnO or TiO2 is added as a sintering aid, there is a risk that these sintering aids will precipitate significantly at the grain boundaries, and it is predicted that the optical performance of rare earth oxide ceramics to which these are added will be insufficient.

[0039] It is said that the difference in the size of an ion that can be stably substituted for a specific ion in the lattice that constitutes a crystal is about ±10%. For example, Y 3+ The ionic radius of Zn is 0.90 Å, so only ions with an ionic radius of 0.99 to 0.81 Å can be substituted. 2+ Or Ti 4+ The ionic radius of these oxides is too small, so it has been considered common technical knowledge to be ineligible for use as sintering aids in synthesizing transparent rare earth oxide ceramics. However, such common technical knowledge is based solely on a thermodynamic viewpoint (equilibrium theory), and the present invention began with the finding or idea of ​​the inventor that the situation is different when synthesizing materials at low temperatures (non-equilibrium).

[0040] Based on the above findings, the present invention + The results are inconceivable according to conventional wisdom, that is, the above-mentioned ion sizes can be effectively used as additives for rare earth oxide ceramics or zirconia ceramics. In particular, with regard to the above-mentioned point that "the difference in ion sizes that can be stably dissolved is about ±10%", "stable" means that there is a wide range of solid solution, and it is acceptable to add a small amount of sintering aids as long as there are no optical problems. Therefore, the application and introduction of this concept to the present invention is a feature that differs from the past.

[0041] As mentioned above, low-temperature synthesis of sintered bodies (low-temperature sintering) not only reduces the energy consumed in synthesis and makes the synthesis equipment cheaper, but is also effective in improving optical quality. However, further improvements are needed to obtain high-quality sintered bodies of rare earth oxides even at lower temperatures.

[0042] For example, when a commercially available Y2O3 raw material with a primary particle size of 0.1 μm is used, (a) no sintering aid is added, and (b) 1% ZrO2 is added, in order to obtain a relative density of 99%, (a) requires 1650°C, and (b) requires 1700°C. In contrast, when 0.1% ZnO is added as in the present invention, a sintered body with the same density can be obtained at 1150°C, and even with 0.1% TiO2 added, it can be obtained at 1300°C. Even when oxides such as Zr and Hf are added as sintering aids, a translucent or transparent body can be obtained, but there are problems as optical materials due to the occurrence of localized heterogeneous phases, grain boundary phases, or segregation of sintering aid components near grain boundaries, and therefore the optical properties are insufficient to be comparable to those of a general single crystal.

[0043] When the additive of the present invention is used and the material is synthesized under appropriate conditions, the optical quality is extremely good because there is substantially no heterogeneous phase or grain boundary phase. By using pre-sintering and HIP (Hot Isostatic Press), high temperatures are not required for pre-sintering, and a sintered body with a relative density of 91% or more can be obtained at a relatively low temperature of about 900 to 1450°C. The HIP processing temperature is also in the range of 900 to 1600°C (for example, about 1200 to 1400°C), which is an innovative low-temperature synthesis process that can make the material transparent. Moreover, a vacuum sintering device using a heating element such as tungsten is not essential, and synthesis can be performed in an inexpensive sintering furnace using a SiC heating element, MoSi heating element, etc. under atmospheric pressure or in an oxygen atmosphere.

[0044] For example, the oxide of Tb (Tb2O3), which is atomic number 65, has a large Verdet constant and can be applied to Faraday elements, which are important in developing small, high-performance isolators. However, since its phase transition point is about 1400°C, low-temperature synthesis below that temperature is essential. Although there are examples of high-density, optical-grade ceramic synthesis at high temperatures of 1500 to 1600°C by adding ZrO2, etc. to this material, optical problems remain because the phase transition point is exceeded, but this invention can solve these problems. In addition, for example, Gd2O3, Eu2O3, etc. have even lower phase transition temperatures and therefore require even lower-temperature synthesis, but this invention also makes it possible to achieve these.

[0045] Furthermore, since oxides with atomic numbers of 58 (Ce) to 62 (Sm) require synthesis at even lower temperatures, the present invention makes it possible to synthesize composite oxide ceramics having a composition in which one or more oxides or composite oxides selected from Sc, Y, and atomic numbers 63 to 71 are combined with oxides with atomic numbers of 58 to 62, as long as the oxides are made of a single oxide or a combination of two or more oxides (composite oxides, mixed oxides) with atomic numbers of 58 to 62.

[0046] As described above, the present invention, which is based on the low-temperature synthesis of dense and transparent rare earth oxide ceramics, makes it possible to provide materials with higher transparency, i.e., less scattering and higher uniformity. This not only makes it possible to synthesize high-quality materials at low temperatures, but also enables the synthesis of substances that were previously thought to be impossible to synthesize due to the existence of phase transitions.

[0047] On the other hand, in the case of zirconia, the present invention makes it possible to provide zirconia ceramics (particularly monoclinic zirconia) that are denser than conventional zirconia ceramics. Generally, it was believed that it was impossible to synthesize a high-density sintered body of zirconia at a firing temperature of 1100°C or less due to phase transition. However, the present invention makes it possible to synthesize zirconia at a relatively low temperature of 1100°C or less, and in particular, by introducing a hot-press sintering method (HIP), it is possible to synthesize a dense zirconia sintered body with a relative density of 99% or more. Since the zirconia ceramics (particularly monoclinic zirconia) of the present invention are dense materials that have never been seen before, it is expected that their applications will be expanded in addition to the applications of zirconia that have been used so far. [Brief description of the drawings]

[0048] [Figure 1] 1 is a diagram showing stable phases of various rare earth elements versus ionic radius and temperature. [Diagram 2] The transmission spectrum of Y2O3 ceramics (t=11 mm) doped with 1000 ppm by weight of ZnO is shown. [Diagram 3] This is a scanning electron microscope (SEM) photograph of a Y2O3 sintered body to which 150 ppm by weight of ZnO and 1200 ppm by weight of TiO2 have been added. [Figure 4] These are transmission polarizing microscope photographs of a Y2O3 sintered body with 150 ppm by weight of ZnO and 1200 ppm by weight of TiO2 added. (a-1) and (a-2) were taken in polarized mode with one polarizing plate, and (b-1) and (b-2) were taken with two polarizing plates crossed. [Diagram 5] The transmission spectra of Y2O3 ceramics (t=1 and 11 mm) and Y2O3 single crystal (t=1 mm) doped with 2000 ppm TiO2 and 1000 ppm CaO by weight are shown. [Figure 6] This is a view seen through a Y2O3 sintered body (diameter 6 inches, thickness 10 mm) that was added with 540 ppm by weight of ZnO and subjected to HIP treatment. [Figure 7]Zirconia ceramics with a relative density of 99.9% and a monoclinic structure, which is made by adding 0.8 wt% ZnO to monoclinic zirconia powder with a primary particle size of 0.05 μm, exhibits translucency in appearance. [Figure 8] FIG. 7 shows an XRD (X-ray Diffraction Pattern) of the ceramic, which exhibits a peak of monoclinic zirconia. [Figure 9] A SEM photograph of the microstructure of the ceramic in FIG. 7 is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0049] 1. Oxide ceramics The oxide ceramic of the present invention (the ceramic of the present invention) is (1) (1-1) a cubic oxide ceramic containing at least one element of the lanthanoid rare earth having atomic number 21 (Sc), atomic number 39 (Y), and atomic number 57 (La) to 71 (Lu), or (1-2) a monoclinic oxide ceramic containing zirconium, (2) The oxide ceramic of (1-1) or (1-2) is (a) At least one of ZnO and Ti oxide: 50 to 10,000 ppm by weight (however, when the element contains the atomic number 65 (Tb), the content of Ti oxide is less than 1,000 ppm by weight); and (b) At least one of MgO, CaO, and SrO: 0 to 0.3% by weight The present invention is characterized by comprising:

[0050] In the following, at least one of ZnO and Ti oxide is referred to as the "first additive", at least one of MgO, CaO and SrO is referred to as the "second additive", and the first additive and the second additive are collectively referred to as the "additive".

[0051] As described above, the ceramics of the present invention are oxide ceramics containing the first additive and, if necessary, the second additive, and can be roughly divided into the above-mentioned (1-1) cubic oxide ceramics (first invention) and (1-2) monoclinic oxide ceramics (second invention) according to the types of their main constituent elements. In the following, for convenience, the first invention and the second invention will be explained separately.

[0052] (A) First Invention (hereinafter referred to as "rare earth oxide ceramics") The rare earth oxide ceramic of the present invention mainly comprises polycrystals (particularly polycrystals having a cubic structure) of at least one rare earth oxide having atomic numbers 21 (Sc), 39 (Y), and 57 (La) to 71 (Lu).

[0053] The composition of the rare earth oxide ceramic of the first invention is preferably such that the total of the rare earth oxide and additives is 99.9% by weight or more. Therefore, the present invention also includes the case where the total is 100% by weight. However, it is permissible for other substances to be contained within a range of 0.1% by weight or less, as long as the effect of the present invention is not impaired.

[0054] The rare earth oxide ceramic of the first invention contains at least one of ZnO and Ti oxide as a first additive in a total amount of 50 to 10,000 ppm by weight, preferably in the range of 50 to 5,000 ppm by weight (however, when the element containing atomic number 65 (Tb) is included as the element, the content of Ti oxide is less than 1,000 ppm by weight). The addition of the first additive not only lowers the sintering temperature and enables low-temperature synthesis, but also makes it possible to obtain a rare earth oxide ceramic (sintered body) with high transparency under appropriate synthesis conditions.

[0055] Both ZnO and Ti oxide (powder) can be known or commercially available. The valence of Ti oxide is not limited, so any of TiO2, TiO, T2O3, etc. can be used.

[0056] As described above, the content of the first additive is preferably 50 to 5000 ppm by weight in total of ZnO and Ti oxide. However, when the element with atomic number 65 (Tb) is included as the element, the content of Ti oxide is less than 1000 ppm by weight, preferably 900 ppm by weight or less.

[0057] In particular, in the present invention, (a) when ZnO is included but Ti oxide is not included, the content is 50 to 2000 ppm by weight, (b) when Ti oxide is included but ZnO is not included, the content is 100 to 5000 ppm by weight, and (c) when both ZnO and Ti oxide are included, the total content is preferably 50 to 5000 ppm by weight. If the amount of the first additive is too small, it becomes difficult to densify the rare earth oxide ceramics, so not only does the sintering temperature increase, but it is also difficult to obtain a translucent sintered body. If the amount of the first additive is too large, abnormal grain growth occurs in the case of ZnO, so even if densified, the particles are large, the mechanical strength is weak, and the optical performance is extremely reduced. If the amount of Ti oxide is too large, the grain boundary precipitation of the Ti-containing double oxide becomes significant, and the optical performance is extremely reduced.

[0058] In particular, when oxides with atomic numbers 22 (Ti) to 30 (Zn) are added as additives to rare earth oxides, coloring and precipitation of the additives at grain boundaries are observed in most cases, making it difficult to obtain colorless and transparent rare earth oxide ceramics. In contrast, when only Ti and Zn are added in appropriate amounts, a sintered body with a relative density of 98% or more can be obtained even at a low temperature of 950°C, and translucency can be imparted to the sintered body with a relative density of 91% or more by HIP treatment at a pressure of 49 to 392 MPa and a temperature of 1000 to 1600°C. In addition, ZnO and TiO2 may be added alone or together. If ZnO is added alone in a range of 50 to 2000 ppm by weight, TiO2 is added alone in a range of 100 to 5000 ppm by weight, and TiO2 is added together in a range of 50 to 5000 ppm by weight, a high density and translucent rare earth oxide ceramic can be obtained relatively easily. ZnO or TiO2 may be added alone or together. Furthermore, the second additive described below may be added together with ZnO or TiO2. Depending on the conditions, adding the second additive together with the first additive can further improve the microstructure, making it possible to produce rare earth oxide ceramics with extremely little scattering.

[0059] In the rare earth oxide ceramic of the first invention, at least one of MgO, CaO and SrO may be contained in the range of 0 to 0.3 wt % as a second additive, if necessary. By using the second additive in combination with the first additive, it is possible to obtain a sintered body with higher transparency (smaller scattering coefficient).

[0060] The rare earth oxide ceramic of the first invention is a polycrystalline body, and the average crystal grain size is preferably about 1 to 50 μm. By setting the average crystal grain size within this range, better optical properties can be obtained.

[0061] The relative density of the rare earth oxide ceramic of the first invention can be appropriately selected depending on, for example, the application and the desired optical properties, but is usually preferably 98% or more. In particular, when the ceramic of the present invention is used for optical applications, the relative density is preferably 99.9% or more, and more preferably 99.99% or more. Furthermore, when the application is a laser, an isolator, or the like, the relative density is most preferably 99.9999% or more.

[0062] In the rare earth oxide ceramic of the first invention, it is preferable that the optical loss is small. For example, it is preferable that the optical loss is 10% / cm or less at a wavelength of 633 nm. Also, it is preferable that the optical loss is 5% / cm or less at a near-infrared wavelength of 1 μm.

[0063] The rare earth oxide ceramic of the first invention has light transmissivity, and in particular, in a sample of the ceramic of the present invention having a thickness of 2 mm, the extinction ratio at a wavelength of 1 μm is preferably 25 dB or more. By having such physical properties, it can be used as an optical material such as a window in the infrared region. This allows a clear image to be obtained without distortion even in window applications that require a simple transmission function. If it has a cubic crystal structure like the ceramic of the present invention, there is theoretically no birefringence and the extinction ratio should be very high, but there are many cases where the extinction ratio is not high because birefringence exists even in general single crystal or polycrystalline ceramics with existing cubic crystal structures. The extinction ratio is important in laser or isolator applications, which are one of the application fields of the present invention, and as described above, it is possible to exhibit an extinction function of 25 dB or more, or even 35 dB or 40 dB or more. In addition, when the ceramic of the present invention is used for applications that do not require high light transmissivity, it is not necessarily necessary to have the above extinction ratio.

[0064] (B) Second Invention (hereinafter referred to as "zirconia ceramics") The zirconia ceramic of the present invention is mainly composed of polycrystals containing zirconia (ZrO2) (particularly polycrystals having a monoclinic structure).

[0065] The composition of the zirconia ceramic of the second invention is preferably such that the total of zirconia, HfO2 derived from the raw material thereof, and additives is 99.8% by weight or more. Therefore, the present invention also includes the case where the total is 100% by weight. Note that, as long as the effect of the present invention is not hindered, it is permissible for other substances to be contained within a range of 0.2% by weight or less. Note that, since zirconia ceramics are not generally used for optical applications, grain boundary segregation of additives is permissible within a range that does not hinder the effect of the present invention.

[0066] The zirconia ceramic of the second invention contains at least one of ZnO and Ti oxide in a total amount of 50 to 10,000 ppm by weight, preferably 2,000 to 10,000 ppm by weight, as a first additive. The addition of the first additive not only lowers the sintering temperature and enables low-temperature synthesis, but also allows for the production of denser zirconia ceramic under appropriate synthesis conditions.

[0067] Both ZnO and Ti oxide (powder) can be known or commercially available. The valence of Ti oxide is not limited, so any of TiO2, TiO, T2O3, etc. can be used.

[0068] As described above, the content of the first additive is preferably 2000 to 10000 ppm by weight in total of ZnO and Ti oxide. If the amount of the first additive is too small, it is difficult to densify the zirconia ceramics, and the sintering temperature increases, so that the ceramics after sintering may have many cracks or collapse. If the amount of the first additive is too large, in the case of ZnO, the formation of a second phase (grain boundary phase) in the vicinity of the grain boundary becomes significant, and it becomes detectable even by XRD analysis, so that some problem may occur in the characteristics.

[0069] In the zirconia ceramic of the second invention, as necessary, at least one of MgO, CaO and SrO is contained as the second additive in the range of 0 to 0.3 wt%, preferably 0 to 0.1 wt%. In the zirconia ceramic of the present invention, both the first additive and the second additive are preferably contained in as small an amount as possible to avoid the formation of a second phase or excessive grain growth. From this viewpoint, it is most preferable that the second additive is contained in substantially 0 wt%.

[0070] The zirconia ceramic of the second invention is a polycrystalline body, and the average crystal grain size is preferably about 0.3 to 5 μm, which allows the formation of zirconia ceramic with a denser structure.

[0071] The relative density of the zirconia ceramic according to the second invention can be appropriately selected depending on, for example, the application, the desired optical properties, etc., but since most ceramics generally industrialized are 98% or more, it is particularly preferable that the relative density be 98% or more. Since the crystal structure of this material is monoclinic, the possibility of optical application is very low, but the relative density can be realized up to about 99.99%.

[0072] 2. Manufacturing method of oxide ceramics The oxide ceramics of the present invention can be suitably produced, for example, by the following production methods. Preferred production methods of the first and second inventions will be described below.

[0073] (A) Manufacturing method of the first invention The rare earth oxide ceramic according to the first aspect of the present invention can be suitably produced by the following production method. That is, the method for producing rare earth oxide ceramic includes the steps of: (1) A process for obtaining a mixture by wet-mixing, in an alcohol, a raw material including (a) a powder of a rare earth element-containing substance having an average primary particle size of 0.05 to 3 μm and (b) a compound including at least one of Zn and Ti; (2) forming the mixture or a dried product thereof into a green compact; (3) pre-sintering the green compact at a temperature of 900 to 1450°C to obtain a pre-sintered body having a relative density of 91 to 99.8%; and (4) A step of subjecting the pre-sintered body to HIP treatment at a temperature of 1000 to 1600°C and a pressure of 98 to 392 MPa. The rare earth oxide ceramic of the present invention can be suitably produced by the production method characterized by comprising the steps of:

[0074] Mixing process In the mixing step, a mixture is obtained by wet-mixing raw materials including (a) a powder of a rare earth element-containing substance having an average primary particle size of 0.05 to 3 μm and (b) a compound containing at least one of Zn and Ti in alcohol.

[0075] The rare earth element-containing substance may be a substance containing at least one element of the lanthanoid rare earths with atomic number 21 (Sc), atomic number 39 (Y), and atomic number 57 (La) to 71 (Lu). Usually, rare earth oxides can be used as the substance, but they are not limited to this as long as they are ultimately oxides, and rare earth compounds such as carbonates, hydroxides, and oxalates can also be used. The purity of the above substance is not limited as long as it does not interfere with the effects of the present invention, but is usually preferably 99.9% or more. These substances can be publicly known or commercially available.

[0076] The rare earth element-containing substance is used in the form of a powder having an average primary particle size of 0.05 to 3 μm (preferably 0.05 to 1 μm). By setting the average primary particle size within this range, a denser sintered body can be obtained.

[0077] In the mixing step, a compound containing at least one of Zn and Ti is used as an additive. These are the supply sources of the first additive. Therefore, the compound may be any compound that is finally converted into an oxide through HIP treatment or the like, and in addition to oxides, compounds such as hydroxides, nitrates, carbonates, chlorides, alkoxides, and acetylacetonates can also be used. More specifically, inorganic compounds such as Zn(OH)2, Ti(OH)4, ZnCl2, and TiOCl2, and organic compounds such as alkoxides and acetylacetonates of Zn or Ti can be used.

[0078] As a preferred embodiment, in the present invention, as the first additive, at least one of (b1) Zn oxide or Ti oxide powder having an average primary particle size equal to or smaller than the average primary particle size of the rare earth oxide powder, (b2) an organic Zn compound or an organic Ti compound, and (b3) a Zn salt or a Ti salt can be suitably used.

[0079] Examples of the above (b1) include ZnO powder, TiO2 powder, and the like having an average primary particle size of 1 μm or less (preferably 0.5 μm or less).

[0080] Examples of (b2) include ZnTi alkoxide compounds, Zn acetylacetonate compounds, organic acid salts of Zn and Ti, etc. More specifically, tetra-n-butoxy(Zn,Ti), (Zn,Ti) propoxide, (Zn,Ti) butoxide, zinc acetylacetonate, titanyl acetylacetonate, etc.

[0081] Examples of (b3) include ZnCl2, TiOCl2, Zn(NO3)2, TiO(NO3)2·2H2O, TiO(CH3COO)2, etc.

[0082] The mixing ratio of the rare earth oxide starting material and the Zn and Ti oxide sources may be adjusted so that the Zn and Ti oxide contents in the finally obtained ceramic of the present invention are as described above. Therefore, when ZnO is added alone, it is preferable to adjust it to 50 to 2000 ppm by weight, and when Ti oxide is added alone, it is preferable to adjust it to 100 to 5000 ppm by weight. When Zn and Ti oxide are used in combination, it is preferable to adjust it to a total amount of 50 to 5000 ppm by weight.

[0083] In addition, in the present invention, when the ceramic of the present invention contains a second additive, a substance that serves as a source of the second additive can be contained in the raw material as necessary. That is, a compound containing at least one of Mg, Ca, and Sr can be blended into the raw material. By adding this, it is possible to improve the microstructure of the obtained sintered body and further improve the optical properties.

[0084] These compounds may be any compounds that eventually become oxides through HIP treatment, etc., and may be, for example, inorganic or organic acid salts such as oxides, hydroxides, carbonates, chlorides, oxalates, acetates, etc., as well as alkoxides, etc. More specifically, at least one of CaO, MgO, SrO, CaCO3, Ca(OH)2, CaCl2, CaC2O4, MgaCO3, Mg(OH)2, MgCl2, MgaC2O4, SrCO3, Sr(OH)2, SrCl2, SrC2O4, etc. may be used.

[0085] The above-mentioned raw materials are mixed by wet mixing in alcohol. As the alcohol, industrial alcohol containing ethanol as a main component (for example, product name "Solmix" (registered trademark, Japan Alcohol Sales Co., Ltd., etc.) is economically effective, but is not particularly limited, and for example, ethanol may be used. The alcohol can be used in the range of about 150 to 300 parts by weight per 100 parts by weight of the total weight of the solid content, but is not limited thereto.

[0086] The above raw materials may contain an organic binder, etc., if necessary. The organic binder is not particularly limited, but for example, a synthetic resin binder such as an acrylic resin binder or a polyvinyl alcohol binder can be suitably used. The amount of the organic binder used may be about 1 to 3 parts by weight per 100 parts by weight of the total weight of the rare earth oxide source and the Zn and Ti oxide source, but is not limited thereto.

[0087] In wet mixing, it is basically desirable to use YTZ (Y partially stabilized zirconia). For example, YTZ with a purity of 99.5% by weight or more can be suitably used. This can minimize contamination from the balls. For the same reason, it is also preferable to use a synthetic resin container or a YTZ container with a purity of 99.5% by weight or more when using grinding media. Therefore, for example, 500 to 2000 parts by weight of YTZ balls with a purity of 99.5% by weight or more and a diameter of 0.5 to 3.0 mm are used per 100 parts by weight of the total weight of the rare earth oxide raw material and the Zn and Ti oxide source, and these are placed in a synthetic resin pot with a purity of 99.5% or more, placed on a rotating stand, and mixed for about 15 to 30 hours to obtain a mixture in the form of a slurry.

[0088] The slurry can be subjected to a drying process, a granulation process, etc., and the resulting slurry can be subjected to a molding process. As the drying process, for example, a method including a process of 1) evaporating the solvent from the slurry at a temperature of 70 to 90°C to obtain a dry powder, and 2) crushing the dry powder and then passing it through a sieve of about 100 mesh to obtain a powder can be used.

[0089] As the granulation process, for example, a method including a step of granulating and drying the slurry can be adopted. As a method for carrying out granulation and drying, for example, a known method such as spray drying can be used. In this case, the average particle size of the granulated material (granules) is not limited, but it is usually desirable to set it to about 10 to 50 μm.

[0090] In the production method of the present invention, any product that is at least dried from the mixture is called a dried product. Therefore, the above-mentioned granulated product is also included in the dried product. The solid content in the dried product can be appropriately adjusted depending on, for example, the type of components constituting the dried product.

[0091] Molding process In the molding step, the mixture or a dried product thereof is molded to obtain a green compact. In the molding step, the mixture or a dried product thereof is molded to obtain a green compact. The molding method is not particularly limited, and various methods such as uniaxial press molding, cold isostatic pressing (CIP molding), slip casting, extrusion molding, and injection molding can be used alone or in combination of two or more. As a combination of two or more molding methods, for example, a green compact can be obtained by performing uniaxial press molding as a primary molding and then performing CIP as a secondary molding.

[0092] In addition, in the molding process, the molding method and its conditions can be appropriately set according to the desired product shape, etc. For example, when forming a smartphone screen, it is possible to knead wax into the raw material without using the dry powder and perform near-net molding by an injection method. For example, when forming an infrared lens, etc., a mold for forming a disk is prepared, and if it is a dome shape, a dome-shaped rubber mold is prepared and then molding is performed.

[0093] The pressure applied during molding can be set appropriately depending on the particle size and composition of the raw material powder used, but it is generally preferable to apply pressure so that the density of the resulting molded body is approximately 45 to 65% of the theoretical density.

[0094] In the present invention, it is desirable to carry out CIP molding, since it can form a relatively uniform density distribution. The molding pressure in the case of CIP molding can be set appropriately within the range of usually 98 to 392 MPa (preferably about 100 to 250 MPa), but is not limited thereto. In addition, in the case of molding in two stages as described above, for example, uniaxial press molding can be carried out using a mold within the range of 5 to 20 MPa, and then CIP molding can be carried out within the range of 98 to 392 MPa.

[0095] The obtained green compact is subjected to a preliminary sintering step. However, when an organic binder is used in the molding step, or when grinding media (particularly media made of synthetic resin) are used, it is preferable to remove organic components by firing the obtained green compact. In this case, the firing (removal of organic matter) conditions are not limited, and can be, for example, about 600 to 800°C in an oxidizing atmosphere.

[0096] Pre-sintering process In the pre-sintering step, the green compact is pre-sintered at a temperature of 900 to 1450° C. to obtain a pre-sintered body having a relative density of 91 to 99.8%.

[0097] The pre-sintering temperature is usually 900 to 1450°C, and preferably 1000 to 1400°C, but may be adjusted appropriately depending on the sintering characteristics of the raw material used. If the temperature is too low, even if a pre-sintered body that is not sufficiently densified (a sintered body with many open pores) is HIPed, the pressure cannot be transmitted to the inside, so the densification itself is insufficient and sufficient transparency cannot be obtained. If the temperature is too high, the constituent particles are too large compared to the size of the residual pores, so the residual pores cannot be efficiently removed, resulting in insufficient densification and transparency. The pre-sintering time may be appropriately set depending on the density and particle size of the pre-sintered body, the size of the green compact, etc.

[0098] In order to achieve these properties, it is common to sinter at high temperatures to produce a denser and more uniform material, but in the present invention, in order to obtain a transparent body, pre-sintering is performed at a lower temperature of 900 to 1450°C. The sintering temperature can be appropriately changed depending on the sinterability of the starting raw material used and the amount of sintered tablets added. For example, when 1000 ppm by weight of ZnO is added to commercially available Y2O3 with an average primary particle size of 0.2 μm, some products reach a relative density of about 98.8% at a pre-sintering temperature of about 1100°C. If the amount of ZnO is reduced to the upper limit of 2000 ppm by weight, the relative density is 94.2% at a pre-sintering temperature of 950°C, realizing low-temperature sintering. The particle size of the pre-sintered material is affected by the temperature and the amount of the first or second additive added, but it is preferable that the average particle size is at least 5 μm or less after pre-sintering, and particularly 1 μm or less.

[0099] The heating rate during pre-sintering can be appropriately set depending on, for example, the sinterability and size of the green compact, but is preferably set to 100° C. / hour or less, particularly in the temperature range of 800° C. or higher. This makes it possible to more effectively reduce the amount of residual porosity.

[0100] The pre-sintering atmosphere is preferably an oxygen-containing atmosphere when ZnO is added, and a hydrogen atmosphere, an oxygen atmosphere, or a vacuum atmosphere when Ti oxide is added, but is more preferably a vacuum atmosphere. The degree of vacuum is not particularly limited, but is preferably 10 -1 ~10 -5 It is preferable to set the pressure to about Pa.

[0101] In particular, in the case of adding Zn, it is preferable to sinter in an atmosphere containing oxygen in order to more reliably obtain a pre-sintered body with a density of 91 to 99.8%. When mixing raw materials to which an organic binder, dispersant, etc. have been added and degreasing the compact, it is necessary to process in air, and when pre-sintering the degreasing green compact, it is necessary to process in air or oxygen. For example, in an N2 gas, hydrogen, or vacuum atmosphere, ZnO evaporates, so the effect of the addition may be lost. In particular, in the case of adding Ti, when pre-sintering after degreasing, any of oxygen, nitrogen, hydrogen, vacuum, etc. can be selected. Of course, when Zn and Ti are added together, it is necessary to process in the same way as when Zn is added alone.

[0102] The pre-sintered body thus obtained is subjected to a HIP process. In this case, the pre-sintered body has a relative density of 91 to 99%, and preferably 94 to 99.8%. Furthermore, it is desirable that the average crystal grain size of the pre-sintered body is 5 μm or less, and preferably 1 μm or less. By pre-sintering within the above-mentioned range of conditions, a material having the characteristics of the present invention can be obtained more reliably.

[0103] HIP treatment process In the HIP treatment step, the pre-sintered body is subjected to HIP treatment at a temperature of 1000 to 1600° C. and a pressure of 98 to 392 MPa.

[0104] When obtaining a transparent body, it is possible to use methods such as SPS (Spark Plasma Sintering) and HP (Hot Press) that apply pressure to make it more dense, but it is preferable to use HIP treatment because it provides the highest quality and is suitable for mass production.

[0105] In principle, the pressure sintering temperature is set to a temperature equal to or lower than the phase transition point of the target substance. In the present invention, however, in cases where the synthesis of a high-density and light-transmitting sintered body by using oxides of elements with atomic numbers of 58 (Ce) to 62 (Sm) alone or a mixture of these elements is not the subject of the present invention, the pre-sintering temperature and pressure sintering temperature can be set in the ranges of 950 to 1450°C and 1000 to 1600°C, respectively.

[0106] In the HIP treatment, the sample after the treatment may be colored due to partial valence change of the added Ti, or due to Zn or Ti being solid-dissolved in the rare earth. Therefore, if coloration occurs after pressure sintering, a nearly colorless translucent rare earth oxide ceramic can be obtained by heat treatment in an oxygen-containing atmosphere at 700 to 1100°C for about 2 to 10 hours. The temperature and time of the heat treatment can be appropriately determined depending on the sample size or the state of coloration during pressure sintering, but if the temperature exceeds 1100°C, the treated sample will rebound (residual pores compressed by the HIP treatment will re-foam due to pressure release), so it is preferable to treat at as low a temperature as possible. In this way, high-density rare earth oxide ceramics can be obtained at a very low temperature, and high-quality optical grade rare earth oxide ceramics can also be synthesized by pressure sintering.

[0107] By HIP sintering the pre-sintered material, a material with translucency can be obtained. The HIP conditions are determined by (i) the amount of sintering aids added in the sintered body, and (ii) the particle size and relative density of the pre-sintered body. If the amount of additives is relatively large and the particle size of the sintered body is small, densification by HIP is promoted at a temperature of about 1000°C, and finally a transparent body is obtained. By optimizing the HIP pressure and holding time, the optical loss can be reduced to 1% / cm or less at a wavelength of 633 nm, and 0.1% / cm or less depending on the conditions, and the optical loss can be reduced to less than that at a wavelength of 1 μm, making it possible to synthesize ultra-high quality materials. For optical materials, the higher the relative density of the sintered body after HIP, the better. In addition, the average particle size after HIP is about 1 to 50 μm, but there is no causal relationship between the average particle size of the sintered body and the optical quality, and there is no problem if it is finished within this range.

[0108] The temperature in the HIP treatment may usually be about 1000 to 1600° C., but if there is no problem with the phase transition temperature of the target material, it is preferable to set it to 1200 to 1600° C. By setting the temperature in this range, the amount and size of pores remaining in the obtained sintered body can be effectively reduced, and at the same time, a microstructure in which grain growth is suppressed can be obtained, resulting in imparting material properties with excellent optical properties.

[0109] The pressure in the HIP treatment is usually 98 to 392 MPa, and particularly preferably 147 to 294 MPa.

[0110] The atmosphere for the HIP treatment is not particularly limited, and may be any of an oxygen-containing atmosphere, an inert gas atmosphere, and the like. Examples of the inert gas atmosphere that may be used include N2 gas and Ar gas. Also, examples of the oxygen-containing atmosphere that may be used include an O2-Ar mixed gas having an oxygen concentration of 20% by volume or less, and an O2-N2 mixed gas having an oxygen concentration of 20% by volume or less. In the present invention, it is particularly preferable to use an atmosphere of an O2-Ar mixed gas or an O2-N2 mixed gas having an oxygen concentration of 20% by volume or less. However, when synthesizing a rare earth oxide ceramic containing Tb2O3, it is preferable that at least a part of Tb is Tb. 4+ Since the optical function is inhibited, a gas containing O2 cannot be used. The lower limit of the oxygen concentration can be, for example, about 10% by volume in either case, but is not limited to this.

[0111] The HIP treatment time is not limited and can be appropriately changed depending on the HIP treatment temperature, etc., but it is usually within the range of 1 to 10 hours.

[0112] In the HIP treatment, the temperature increase rate and the temperature decrease rate are not particularly limited, but are usually sufficient if they are about 300 to 600° C. / hr.

[0113] Annealing process In the present invention, the sintered body after HIP treatment can be subjected to annealing treatment as necessary. In HIP treatment using a carbon heater and inert gas, the material is sometimes reduced and may turn gray or other colors (especially when N2 gas, Ar gas, or the like that does not introduce oxygen is used for HIP treatment), so the sintered body obtained by the HIP treatment can be annealed at 700 to 1100°C. By carrying out the annealing step, lattice defects, distortion, etc. that may exist inside the sintered body can be more reliably removed, resulting in a more transparent sintered body.

[0114] The annealing temperature is usually 700 to 1100°C, and preferably 800 to 1000°C. The treatment atmosphere may be an oxygen-containing atmosphere, and is preferably carried out at a temperature lower than the HIP treatment temperature. There are no particular restrictions on the pressure, but the annealing is usually carried out under atmospheric pressure (normal pressure). The annealing time can be changed as appropriate depending on, for example, the size of the sintered body, the treatment temperature, etc., but is usually within the range of about 3 to 10 hours. As an exception, materials containing Tb may be annealed by dissolving Tb during annealing. 4+ is formed, which increases light absorption in the visible to infrared range, so annealing is not applicable to such materials.

[0115] The annealed sintered body can be used as a predetermined optical material as it is or after being processed into a predetermined shape as necessary. The processing method is not particularly limited, and can be carried out according to a known cutting method, polishing method, etc.

[0116] (B) Manufacturing method of the second invention The zirconia ceramic of the second invention can be suitably produced by the following production method. That is, a method for producing zirconium oxide ceramic, comprising the steps of: (1) (a) a step of wet-mixing a raw material containing monoclinic zirconia powder having an average primary particle size of 0.02 to 0.2 μm and (b) a compound containing at least one of Zn and Ti in an alcohol to obtain a mixture (mixing step); (2) forming the mixture or a dried product thereof into a green compact (forming step); and (3) A step of sintering the green compact at a temperature of 1000 to 1100°C to obtain a sintered compact having a relative density of 92 to 99.8% (sintering step). The zirconia ceramic according to the second aspect of the present invention can be suitably produced by the production method comprising the steps of:

[0117] Mixing process In the mixing step, a mixture is obtained by wet-mixing raw materials including (a) monoclinic zirconia powder having an average primary particle size of 0.02 to 0.2 μm and (b) a compound containing at least one of Zn and Ti in alcohol.

[0118] In the manufacturing method of the present invention, monoclinic zirconia powder can be suitably used as the zirconia supply source. The purity of the powder is not limited as long as it does not interfere with the effects of the present invention, but is usually preferably 99.9% or more. Such powder can be a publicly known or commercially available one.

[0119] The average primary particle size of the monoclinic zirconia powder is 0.02 to 0.2 μm (preferably 0.02 to 0.1 μm). By setting the average primary particle size within this range, a denser sintered body can be obtained.

[0120] In the mixing step, a compound containing at least one of Zn and Ti is used as an additive. These are the supply sources of the first additive. Therefore, the compound may be any compound that is finally converted into an oxide through HIP treatment or the like, and in addition to oxides, compounds such as hydroxides, nitrates, carbonates, chlorides, alkoxides, and acetylacetonates can also be used. More specifically, inorganic compounds such as Zn(OH)2, Ti(OH)4, ZnCl2, and TiOCl2, and organic compounds such as alkoxides and acetylacetonates of Zn or Ti can be used.

[0121] As a preferred embodiment, in the present invention, as the first additive, at least one of (b1) Zn oxide or Ti oxide powder having an average primary particle size equal to or smaller than the average primary particle size of the rare earth oxide powder, (b2) an organic Zn compound or an organic Ti compound, and (b3) a Zn salt or a Ti salt can be suitably used.

[0122] Examples of the above (b1) include ZnO powder, TiO2 powder, and the like having an average primary particle size of 1 μm or less (preferably 0.5 μm or less).

[0123] Examples of (b2) include ZnTi alkoxide compounds, Zn acetylacetonate compounds, organic acid salts of Zn and Ti, etc. More specifically, tetra-n-butoxy(Zn,Ti), (Zn,Ti) propoxide, (Zn,Ti) butoxide, zinc acetylacetonate, titanyl acetylacetonate, etc.

[0124] Examples of (b3) include ZnCl2, TiOCl2, Zn(NO3)2, TiO(NO3)2·2H2O, TiO(CH3COO)2, etc.

[0125] The mixing ratio of the monoclinic zirconia powder and the Zn and Ti oxide sources may be adjusted so that the Zn and Ti oxide contents in the finally obtained ceramic of the present invention are as described above. Therefore, when ZnO is added alone, it is preferable to adjust it to 50 to 2000 ppm by weight, and when Ti oxide is added alone, it is preferable to adjust it to 100 to 5000 ppm by weight. When Zn and Ti oxide are used in combination, it is preferable to adjust it to a total amount of 50 to 5000 ppm by weight.

[0126] In the present invention, when the ceramic of the present invention contains a second additive, a substance that serves as a source of the second additive can be contained in the raw material as necessary. That is, a compound containing at least one of Mg, Ca, and Sr can be blended in the raw material.

[0127] These compounds may be any compounds that eventually become oxides through HIP treatment, etc., and may be, for example, inorganic or organic acid salts such as oxides, hydroxides, carbonates, chlorides, oxalates, acetates, etc., as well as alkoxides, etc. More specifically, at least one of CaO, MgO, SrO, CaCO3, Ca(OH)2, CaCl2, CaC2O4, MgaCO3, Mg(OH)2, MgCl2, MgaC2O4, SrCO3, Sr(OH)2, SrCl2, SrC2O4, etc. may be used.

[0128] The above-mentioned raw materials are mixed by wet mixing in alcohol. As the alcohol, industrial alcohol containing ethanol as a main component (for example, product name "Solmix" (registered trademark, Japan Alcohol Sales Co., Ltd., etc.) is economically effective, but is not particularly limited, and for example, ethanol may be used. The alcohol can be used in the range of about 150 to 300 parts by weight per 100 parts by weight of the total weight of the solid content, but is not limited thereto.

[0129] The above raw materials may contain an organic binder, etc., if necessary. The organic binder is not particularly limited, but for example, a synthetic resin binder such as an acrylic resin binder or a polyvinyl alcohol binder may be suitably used. The amount of the organic binder used may be about 1 to 3 parts by weight per 100 parts by weight of the total weight of the monoclinic zirconia powder and the Zn and Ti oxide supply sources, but is not limited thereto.

[0130] In wet mixing, it is preferable to use YTZ (Y partially stabilized zirconia) balls as a grinding and mixing medium. For example, YTZ balls with a purity of 99.5% by weight or more can be suitably used. This can minimize contamination from the balls. For the same reason, it is preferable to use a synthetic resin container or a YTZ container with a purity of 99.5% by weight or more when using grinding media. Therefore, for example, 500 to 2000 parts by weight of YTZ balls with a purity of 99.5% by weight or more and a diameter of 0.5 to 3.0 mm are used for 100 parts by weight of the total weight of the monoclinic zirconia powder and the Zn and Ti oxide source, and these are placed in a synthetic resin pot with a purity of 99.5% or more, placed on a rotating stand, and mixed for about 15 to 30 hours to obtain a mixture in the form of a slurry.

[0131] The slurry can be subjected to a drying process, a granulation process, etc., and the resulting slurry can be subjected to a molding process. As the drying process, for example, a method including a process of 1) evaporating the solvent from the slurry at a temperature of 70 to 90°C to obtain a dry powder, and 2) crushing the dry powder and then passing it through a sieve of about 100 mesh to obtain a powder can be used.

[0132] As the granulation process, for example, a method including a step of granulating and drying the slurry can be adopted. As a method for carrying out granulation and drying, for example, a known method such as spray drying can be used. In this case, the average particle size of the granulated material (granules) is not limited, but it is usually desirable to set it to about 10 to 50 μm.

[0133] In the production method of the present invention, any product that is at least dried from the mixture is called a dried product. Therefore, the above-mentioned granulated product is also included in the dried product. The solid content in the dried product can be appropriately adjusted depending on, for example, the type of components constituting the dried product.

[0134] Molding process In the molding step, the mixture or a dried product thereof is molded to obtain a green compact. In the molding step, the mixture or a dried product thereof is molded to obtain a green compact. The molding method is not particularly limited, and one or more of various methods such as uniaxial press molding, cold isostatic pressing (CIP molding), slip casting, extrusion molding, and injection molding can be used in combination. As a combination of two or more molding methods, for example, a green compact can be obtained by performing uniaxial press molding as a primary molding and then performing CIP as a secondary molding.

[0135] In addition, in the molding process, the molding method and its conditions can be appropriately set according to the desired product shape, etc. For example, when forming an infrared lens, window material, dome, etc., a metal mold for forming a disk is prepared, and if it is a dome shape, a dome-shaped rubber mold is prepared and then molding is performed.

[0136] The pressure applied during molding can be set appropriately depending on the particle size and composition of the raw material powder used, but it is generally preferable to apply pressure so that the density of the resulting molded body is approximately 45 to 65% of the theoretical density.

[0137] In the present invention, it is desirable to carry out CIP molding, since it can form a relatively uniform density distribution. The molding pressure in the case of CIP molding can be set appropriately within the range of usually 98 to 392 MPa (preferably about 100 to 250 MPa), but is not limited thereto. In addition, in the case of molding in two stages as described above, for example, uniaxial press molding can be carried out using a mold within the range of 5 to 20 MPa, and then CIP molding can be carried out within the range of 98 to 392 MPa.

[0138] The obtained green compact is subjected to a preliminary sintering step. However, when an organic binder is used in the molding step, or when grinding media (particularly media made of synthetic resin) are used, it is preferable to remove organic components by firing the obtained green compact. In this case, the firing (removal of organic matter) conditions are not limited, and can be, for example, about 600 to 800°C in an oxidizing atmosphere.

[0139] Sintering process In the sintering step, the green compact is pre-sintered at a temperature of 1000 to 1100° C. to obtain a sintered body having a relative density of 92 to 99.8%.

[0140] The sintering temperature is usually about 1000 to 1100°C, and preferably 1050 to 1100°C, but may be adjusted appropriately depending on the sintering characteristics of the raw materials used. If the temperature is too high, it will exceed the phase transition temperature, causing cracks or collapse of the sample after sintering. If the temperature is too low, densification will be insufficient, as with rare earth oxide ceramics.

[0141] The particle size of the raw material powder is not limited, but since the upper limit sintering temperature for zirconia ceramics is limited to 1100°C, the primary particle size of the starting material used is in the range of 30 to 300 nm. Even if such fine powder is used as the starting material, it is impossible to densify the zirconia at 1100°C or less, even if only zirconia or alumina, which is a general sintering aid for zirconia, is added to the zirconia. In contrast, in the present invention, a dense sintered body of 92% or more can be easily obtained by adding specific amounts of Zn and Ti oxides.

[0142] The heating rate during sintering can be appropriately set depending on, for example, the sinterability and size of the green compact, but is preferably set to 100° C. / hour or less, particularly in the temperature range of 800° C. or higher. This makes it possible to more effectively reduce the amount of residual porosity.

[0143] The sintering atmosphere is not particularly limited, but since the base material, zirconia, itself is a material with a large oxygen diffusion coefficient, it is preferable to carry out the sintering in an oxidizing atmosphere in order to make the most of this characteristic during the sintering process, and it is particularly preferable to carry out the sintering in an oxygen atmosphere (particularly an oxygen content of 20 volume % or more, for example, 20 to 100 volume %).

[0144] In particular, in the case of adding Zn, it is preferable to sinter in an atmosphere containing oxygen in order to obtain a sintered body with a relative density of 92 to 99.8%. When mixing raw materials to which an organic binder, dispersant, etc. have been added, the green body is degreased, and when the degreased green compact is presintered, it must be treated in air or oxygen. In an N2 gas, hydrogen, or vacuum atmosphere, ZnO evaporates, so the effect of the addition is lost. In particular, in the case of adding Ti, any of oxygen, nitrogen, hydrogen, or vacuum can be selected for presintering after degreasing. Of course, when Zn and Ti are added together, it is necessary to treat it in the same way as when Zn is added alone. In this way, the zirconia ceramic of the second invention can be obtained, but the obtained sintered body can also be subjected to the HIP treatment described below as necessary.

[0145] HIP treatment process In the HIP treatment step, the sintered body can be HIP-treated at a temperature of 1000 to 1100°C and a pressure of 98 to 392 MPa. When the HIP treatment step is included, the sintering step can also be called a "pre-sintering step", and the sintered body obtained thereby can also be called a "pre-sintered body".

[0146] A denser material can be obtained by HIP sintering the sintered material. The HIP conditions are determined by (i) the amount of additives added in the sintered body, and (ii) the particle size and relative density of the sintered body. If the amount of additives added is relatively large and the particle size of the sintered body is small, densification by HIP at a temperature of about 1000°C is desirable.

[0147] The temperature in the HIP treatment is usually about 1000 to 1100° C., and preferably 1050 to 1100° C. By setting the temperature in this range, the amount and size of pores remaining in the obtained sintered body can be effectively reduced, and at the same time, a microstructure in which grain growth is suppressed can be obtained, so that a dense zirconia ceramic can be suitably obtained.

[0148] The pressure in the HIP treatment is usually about 98 to 392 MPa, and preferably 147 to 294 MPa.

[0149] The atmosphere for the HIP treatment is not particularly limited, and may be, for example, an oxygen-containing atmosphere, an inert gas atmosphere, or the like. For example, N2 gas, Ar gas, or the like may be used as the inert gas atmosphere. For the oxygen-containing atmosphere, an O2-Ar mixed gas having an oxygen concentration of 20% by volume or less, or an O2-N2 mixed gas having an oxygen concentration of 20% by volume or less may be preferably used. In the present invention, it is more preferable to use an atmosphere of an O2-Ar mixed gas or an O2-N2 mixed gas having an oxygen concentration of 20% by volume or less. The lower limit of the oxygen concentration may be, for example, about 10% by volume in either case, but is not limited thereto.

[0150] The HIP treatment time can be appropriately changed depending on the HIP treatment temperature, etc., but it is usually sufficient to set it within the range of 1 to 10 hours.

[0151] In the HIP treatment, the temperature increase rate and the temperature decrease rate are not particularly limited, but are usually sufficient if they are about 300 to 600° C. / hr.

[0152] Annealing process When manufacturing zirconia ceramics, annealing is usually not required, but can be performed if necessary. That is, the sintered body obtained by the HIP treatment can be annealed. By performing the annealing step, lattice defects, distortion, etc. that may exist inside the sintered body can be more reliably removed, resulting in a denser sintered body.

[0153] The annealing temperature is not particularly limited, but is usually about 700 to 1100°C, and is preferably 800 to 1000°C. Furthermore, it is desirable to perform the annealing at a temperature lower than the HIP treatment temperature. The treatment atmosphere is not particularly limited, but is preferably an oxygen-containing atmosphere. The pressure is not particularly limited, but is usually performed under atmospheric pressure (normal pressure). The annealing time can be appropriately changed depending on, for example, the size of the sintered body, the treatment temperature, etc., but is usually within the range of about 3 to 10 hours.

[0154] The annealed sintered body can be used as a predetermined optical material as it is or after being processed into a predetermined shape as necessary. The processing method is not particularly limited, and can be carried out according to a known cutting method, polishing method, etc.

[0155] 3. Use of the ceramics of the present invention The rare earth oxide ceramics of the present invention can be used for various applications. For example, it can be used as a window material for visible to infrared (about 8 μm). In particular, a transparent body in which at least one oxide of Gd, Lu, Sc, Y, etc. is used as a host and at least one oxide of fluorescent elements such as Nd, Yb, Er, etc. is added can be suitably used as a laser medium or a scintillator medium. In addition, a transparent body containing at least one of Tb, Dy, Ho, etc. can be suitably used as a Faraday rotator of an isolator device that can shut down return waves for fiber lasers or solid-state lasers. In addition, it can be suitably used as various optical materials, etc.

[0156] In the present invention, the phase transition points of rare earth oxide ceramics containing single oxides of Tb, Eu, Gd, etc. or large amounts of these elements are relatively low, making it possible to synthesize ceramics that have been considered difficult to synthesize up until now.

[0157] Furthermore, with regard to the zirconia ceramics of the present invention, there have been no examples of successful synthesis of dense monoclinic polycrystals, and therefore detailed physical properties of such polycrystals remain unknown. However, if the physical properties of the monoclinic zirconia ceramics that can be synthesized according to the present invention are further elucidated, it is expected that the applications of zirconia ceramics will be further expanded.

[0158] <Embodiments of the ceramic of the present invention> To produce the ceramics of the present invention, lanthanoid rare earth oxide raw materials with atomic numbers 21 (Sc), 39 (Y), and 57 (La) to 71 (Lu) are prepared with a purity of 99.9% by weight or more and an average particle size of 0.1 to 3 μm. Basically, ZnO or Ti oxide is added to these rare earth oxide raw materials, either alone or in combination. However, by adding alkoxides of Zn or Ti in the form of particles with an average particle size of 1 μm or less (particularly 0.5 μm or less) or salts such as ZnCl2 and TiOCl2 (titanium oxychloride) as a supply source of Zn and Ti oxide, they can be finally contained as oxides in the alumina ceramics.

[0159] However, for the purpose of improving the optical characteristics (particularly uniformity) of the material, it is preferable to add ZnO or Ti oxide having an average particle size smaller than that of the rare earth oxide particles.

[0160] When adding the above oxides, it is preferable to use ZnO or Ti oxide with as small a particle size as possible. For this reason, it is preferable to set the average particle size of the raw material to 1 μm or less, and particularly 0.5 μm or less.

[0161] When the above alkoxides or the like are added, an appropriate amount of Zn or Ti alkoxide may be added so that the ZnO and / or TiO2 content in the ceramic of the present invention becomes a predetermined amount.

[0162] In the case of c above, for example, zinc chloride (ZnCl 2 ), titanium oxychloride (TiOCl2), titanium oxynitrate (TiO(NO3)2·2H2O), titanium oxyacetate (TiO(CH3COO)2), etc. Compounds (hydroxides or oxides) such as ZnC2O4·2H2O (zinc oxalate), Zn(OH)2, Ti(OH)4, TiO, Ti2O3, etc. can also be used.

[0163] In the present invention, the sintering temperature (densification temperature) can be effectively lowered by adding ZnO, so that the pre-sintering temperature of most rare earth oxide ceramics can be lowered to 1200°C or less by adding ZnO up to the upper limit of 2000 ppm by weight. However, if the ZnO concentration is high, grain growth occurs if the HIP processing temperature is high, and the optical properties may become poor, so it is desirable to suppress it to about the pre-sintering temperature to +100°C. If the amount of ZnO added is small, densification and grain growth are suppressed, so the pre-sintering temperature and HIP temperature may be appropriately determined within the range where the relative density is 91 to 99%. In the case of adding TiO2, the amount of addition does not have a strong effect on the pre-sintering temperature, so it may be appropriately determined within the range of 100 to 5000 ppm by weight depending on the type of rare earth oxide, the particle size of the starting material, etc.

[0164] After adding the zirconia source shown in a) to c) above, an appropriate amount of organic binder and ethyl alcohol are added, and the mixture is ground and mixed for 15 to 30 hours using, for example, 99.9% high purity zirconia balls to obtain a uniform slurry. The obtained slurry is sprayed and dried in a spray dryer to obtain spherical granules of about 20 to 50 μm.

[0165] On the other hand, the preparation of dense monoclinic zirconia ceramic powder is basically the same as that of rare earth oxide ceramics. The zirconia ceramic of the second invention has a monoclinic crystal structure after sintering, and when it is not for optical use, it is possible to add more of the first additive than the rare earth oxide ceramic, which allows the sintering temperature to be set at 1100°C or lower, which is the upper limit of the phase transition point. The processing method of the raw material powder to which the first additive etc. have been added may be the same as that of the rare earth oxide ceramics.

[0166] The obtained granules are molded in a metal mold, and uniaxially molded at a pressure of 10-20 MPa using a metal mold with a diameter of 12 mm to produce a green body (compressed powder) with a thickness of approximately 20 mm. The green body is CIP molded at a pressure of 98-196 MPa, and then degreased in an oxygen-containing atmosphere at a temperature of 700-900°C for 3 hours to remove organic components such as organic binders. Furthermore, when ZnO is added, it is sintered in an oxygen-containing gas at 900-1400°C for approximately 2-5 hours, and when TiO2 is added, it is sintered in an oxygen-containing gas in the same way as when ZnO is added, or sintered at 100°C for approximately 2 hours. -2 ~10 -5 The pre-sintered body is sintered in a vacuum of 1,100 to 1,450°C for 2 to 5 hours at 1,000 Pa to obtain a pre-sintered body with a density of 91 to 99%. The pre-sintered body is then subjected to HIP treatment (gas pressure of 98 to 392 MPa) at 900 to 1,600°C (particularly 1,000 to 1,600°C) for 1 to 5 hours to obtain an ultra-dense sintered body with residual porosity of 1,000 ppm or less, and as a result, a transparent sintered body can be obtained.

[0167] On the other hand, in the synthesis of the zirconia ceramics according to the second invention, zirconia itself, which is the base material, has reduced oxygen diffusion in a non-oxidizing atmosphere, so sintering in an atmosphere containing oxygen (preferably an oxygen atmosphere) is desirable. To obtain a relatively dense pre-sintered body with a relative density of 91% or more, the firing temperature must be 1000°C or higher, but the upper limit is limited to 1100°C or lower due to the problem of phase transition. The sintering time depends on the type and amount of additives, but since there is a limit to the sintering temperature, it is particularly desirable to set it to about 3 to 100 hours.

[0168] Figure 3 shows a SEM photograph of a representative sample obtained by the present invention, a Y2O3 ceramic with 150 ppm ZnO and 1200 ppm TiO2 added. The average grain sizes are about 2 and 1 μm, respectively, and no residual pores are present within the observed field of view.

[0169] Figures 4 (a-1) and (b-1) are transmission polarizing microscope photographs of the Y2O3 ceramics shown in Figure 3 to which 150 ppm by weight of ZnO and 1200 ppm by weight of TiO2 have been added. The birefringence is at a level that is impossible to detect, no residual pores are detected within the observation field, and an extremely high-density sintered body has been formed. (a-2) and (b-2) are images of the birefringence inside the material observed by crossing two polarizing plates. Since birefringence is undetectable in this material, the optical performance is so good that even leakage light cannot be detected when the polarizing plates are crossed. The extinction ratio of both materials is extremely high at >35 dB.

[0170] Figure 5 shows the transmission spectra of Y2O3 ceramics (sample thickness 1mm, 11mm) with 2000 ppm TiO2 and 1000 ppm CaO, and a commercially available Y2O3 single crystal (sample thickness 1mm) produced by the Verneuil method. When comparing single crystal and polycrystalline ceramics of the same thickness, the transmittance of polycrystalline ceramics with grain boundaries is higher over the entire measurement wavelength range. The 11mm thick sample has a slightly larger optical loss at wavelengths of 800nm ​​or less, and the optical loss at a wavelength of 633nm is 2.4% / cm. Since the transmittance of 1mm thick polycrystalline ceramics is higher than that of single crystals, it is reasonable to consider the optical loss of the product of the present invention obtained at a wavelength of 633nm to be lower (high performance) than that of single crystals. As mentioned above, it is difficult to improve the quality of single crystals due to the problem of phase transition, and furthermore, since only a size of about 6mm diameter x 1mm thickness can be synthesized, it is practically impossible to put them to practical use. Moreover, at wavelengths of 900 nm or more, the transmittance of each sample appears to be at the same level, but the optical loss of this material at a wavelength of 1 μm is 0.07% / cm, an astonishing figure for a polycrystalline material.In addition, the wavefront distortion measured using an interferometer is 0.06 λ / cm, demonstrating unprecedented optical uniformity.

[0171] Figure 6 shows an outdoor view seen through a Y2O3 sintered body (diameter 6 inches, thickness 10 mm). This sintered body was produced by adding 540 ppm by weight of ZnO to the Y2O3 raw material, pre-sintering it in pure oxygen at 1200°C for 4 hours, HIPing it at 1290°C for 3 hours (pressure 196 MPa) using N2 gas as a medium, and then heat-treating it in oxygen at 950°C for 5 hours. The sintered body was then mirror-polished on both sides of the 6-inch diameter surface to adjust the thickness to 10 mm. The obtained sintered body is transparent and has an optical loss of <1% / cm at a wavelength of 1 μm, so it can be used as an infrared-transmitting window material for wavelengths of 1 μm or more.

[0172] 7 to 9 show the observation results of zirconia ceramics with a monoclinic crystal structure. This zirconia ceramic was produced by adding 0.8% by weight of ZnO powder with an average particle size of 0.1 μm to zirconia powder with an average primary particle size of 0.05 μm, sintering in pure oxygen at 1080°C for 8 hours, and then HIPing at 1070°C for 2 hours (pressure 180 MPa) using Ar as a pressure medium. The relative density reaches 99.9%. When LED white light is irradiated from below the zirconia ceramic, light transmission can be confirmed (FIG. 7). When this material is analyzed by X-ray diffraction, it can be confirmed that it is composed only of a monoclinic structure, as shown in FIG. 8. In addition, FIG. 9 is an SEM photograph of the microstructure (fracture surface) of the obtained sintered body, and it was confirmed that the surface is a dense structure with almost no residual pores, and the average particle size is 0.5 μm. There have been no examples of the synthesis of dense monoclinic zirconia sintered bodies, and this invention is considered to be the first successful example.

[0173] In the following, as representative examples, concrete examples of the synthesis of transparent Y2O3 ceramics and high-density transparent Gd2O3 ceramics, which have a phase transition temperature of 1200°C and have not been able to be synthesized so far, are shown. In particular, Y2O3 has a stable cubic crystal structure from room temperature to around 2200°C, so it is thought to be easy to produce from the viewpoint of synthesis temperature, but it is not easy to synthesize a material with high optical quality. Generally, low-temperature synthesis requires the use of nano-sized raw materials and processing at as high pressure as possible. In fact, for example, when ZrO2 is used as a sintering aid, the Y2O3 raw material must be pre-sintered at 1500-1600°C even at the level of several tens of nanometers, and then HIP-treated at about 1600-1700°C.

[0174] As a representative example, Y2O3 raw material with an average primary particle size of 0.2 μm was used, to which ZnO with an average primary particle size of 0.5 μm was added at 1000 ppm by weight, and zirconia balls, an appropriate amount of organic binder, dispersant, and ethanol (2 to 3 times the powder weight) were added as grinding and mixing media, and mixed in a ball mill for 15 hours. The resulting slurry was heated to evaporate the solvent while stirring, resulting in a dried powder. This powder was molded into a diameter of 10 mm and a height of 20 mm, and then CIP molded at a pressure of 98 MPa. The molded body was degreased in air at 700 °C for 3 hours to remove organic components from the green compact. The green compact was placed in a tubular furnace capable of controlling the atmosphere in an alumina tube, and sintered in a pure oxygen atmosphere at 1150 °C for 2 hours to obtain a sintered body with a relative density of 98.5%. (Even a sintered body with this density can be used as an insulating material.) The pre-sintered body obtained was subjected to HIP treatment at 1350℃ for 3 hours (176MPa) using Ar as the pressure medium to obtain a transparent body. Since the HIP-treated sintered body was slightly reddish, it was heat-treated in air at 950℃ for 3 hours to obtain a sample that appeared colorless and transparent.

[0175] Figure 2 shows the transmission spectrum of this sample (11 mm thick) after both end faces have been optically polished. The transmittance at 633 nm is 77.2%, and at a wavelength of 1 μm it reaches 80.9%. A 1 mm thick sample was also prepared, and the optical loss was calculated from the difference in thickness, yielding 2.5% / cm at a wavelength of 633 nm and 0.5% / cm at a wavelength of 1 μm, indicating that an extremely high quality material was obtained. This material has sufficient optical properties for use as a window material in the visible to infrared range.

[0176] In the second example, Y2O3 raw material with an average primary particle size of 0.5μm was used, to which 100 ppm by weight of ZnO with an average primary particle size of 0.5μm and 1800 ppm by weight of CaCO3 (approximately 1000 ppm by weight in terms of CaO) were added, and zirconia balls and an appropriate amount of organic binder, dispersant, and ethanol (2 to 3 times the powder weight) were added as grinding and mixing media, and mixed in a ball mill for 20 hours. The resulting slurry was heated to evaporate the solvent while stirring, resulting in a dried powder. This powder was molded into a diameter of 10mm and a height of 20mm, and then CIP molded at a pressure of 147MPa. The obtained green compact was degreased in air at 700℃ for 3 hours to remove the organic components in the green compact. The green compact was placed in a tubular furnace capable of controlling the atmosphere in an alumina tube, and sintered in a pure oxygen atmosphere at 1390℃ for 2 hours to obtain a sintered body with a relative density of 97.7%. (Even a sintered body with this density can be used as an insulating material.) The pre-sintered body obtained was subjected to HIP treatment at 1600℃ for 3 hours (147MPa) using Ar as the pressure medium to obtain a transparent body. Since the HIP-treated sintered body was slightly reddish, it was heat-treated in air at 980℃ for 3 hours to obtain a sample that appeared colorless and transparent.

[0177] In the same manner as described above, samples with a thickness of 11 mm and 1 mm were also prepared, and the optical losses at wavelengths of 633 nm and 1 μm, respectively, were calculated based on the difference in thickness, yielding values ​​of 0.9% / cm and 0.06% / cm, indicating that very high quality materials were obtained.

[0178] In the third example, Y2O3 (95%) with an average primary particle size of 0.5 μm and Er2O3 (5%) with an average primary particle size of 0.1 μm were used as raw materials, to which 900 ppm by weight of TiO2 with an average primary particle size of 0.5 μm was added, and zirconia balls and an appropriate amount of organic binder, dispersant, and ethanol (2 to 3 times the powder weight) were added as grinding and mixing media, and mixed in a ball mill for 20 hours. The resulting slurry was stirred while heating to evaporate the solvent, resulting in a dried powder. This powder was molded into a diameter of 10 mm x 20 mm, and then CIP molded at a pressure of 98 MPa. The molded body was degreased in air at 700 °C for 3 hours to remove the organic components in the green compact. It was placed in a vacuum furnace with a tungsten heater and cooled to 1 × 10-3 The pre-sintered body was sintered at 1350°C for 2 hours under a vacuum of 100 Pa, resulting in a sintered body with a relative density of 96.6%. (Even a sintered body with this density can be used as an insulating material.) The pre-sintered body obtained was HIP-treated at 1550°C for 3 hours (198 MPa) using Ar as the pressure medium, resulting in a transparent body. Since the HIP-treated sintered body was slightly greenish, it was heat-treated in oxygen at 1000°C for 3 hours, resulting in a sample that was apparently colorless and transparent.

[0179] As in the previous section, samples with a thickness of 11 mm and 1 mm were also prepared, and the optical losses at wavelengths of 633 nm and 1 μm were calculated from the difference in thickness, yielding extremely high quality materials with values ​​of 1.1% / cm and 0.1% / cm, respectively, which can be used as a laser oscillation medium.

[0180] In the fourth example, Gd2O3 raw material with an average primary particle size of 0.3 μm was used, to which 900 ppm by weight of ZnO with an average primary particle size of 0.05 μm was added, and zirconia balls and an appropriate amount of organic binder, dispersant, and ethanol (2 to 3 times the amount of powder weight) were added as grinding and mixing media, and mixed in a ball mill for 20 hours. The resulting slurry was heated and evaporated to obtain a dried powder while stirring. This powder was molded into a 10 mm x 15 mm die, and then CIP molded at a pressure of 147 MPa. The molded body was degreased in air at 700 °C for 3 hours to remove organic components in the green compact. After that, this green compact was placed in a tubular furnace with an atmosphere controllable in an alumina tube, and sintered in a pure oxygen atmosphere at 950 °C for 5 hours to obtain a sintered body with a relative density of 98.8%. (Even sintered bodies of this density can be used as insulating materials.) The pre-sintered body obtained was subjected to HIP treatment at 1050℃ for 3 hours (147MPa) using 20% ​​O2-Ar as the pressure medium, resulting in a transparent body. The HIP-treated sintered body was colorless and transparent.

[0181] In the same manner as above, samples with a thickness of 11 mm and a thickness of 1 mm were also prepared, and the optical losses at wavelengths of 633 nm and 1 μm were calculated from the difference in thickness, resulting in a transparent material with a value of 6.6% / cm and 2.0% / cm. This material is used in general light-transmitting window materials as well as in high-density (7.41 g / cm3 ), it can also be used for radiation shutdown windows. Since the orthorhombic to cubic phase transition temperature of Gd2O3 is around 1200℃, it is not only impossible to produce single crystals by the conventional melting and solidification method, but there have been no successful examples of production by the sintering method.

[0182] When producing the zirconia ceramics according to the second invention, a monoclinic zirconia raw material is used, and the total amount of ZrO2 and HfO2 (HfO2 is an inevitable impurity of the same group derived from natural raw materials) is adjusted to a purity of 99.8% by weight or more, and Zn oxide alone or Zn oxide and Ti oxide are added in combination. These additives may be added in the form of the oxide powder, or the additives may be incorporated in advance into the zirconia powder by, for example, a coprecipitation method when synthesizing the zirconia powder. Also, as in the case of synthesizing rare earth oxide ceramics, organic compounds or salts of Zn and Ti may be used. EXAMPLES

[0183] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0184] Example 1 As a raw material, commercially available Y2O3 powder (purity > 99.95%, average primary particle size 0.2μm) was used. ZnO powder (purity: 99.9%, average primary particle size 0.5μm) was added to this powder as a first additive at 50 ppm by weight, and 2 parts by weight of a commercially available acrylic resin binder (20% solution of acrylic resin) and 0.5 parts by weight of a dispersant (Floren GW1500, manufactured by Kyoeisha Chemical Co., Ltd.) were added to 100 parts by weight of these mixed powders, and the mixture was placed in a synthetic resin container. 1 kg of high-purity TYZ (Y-stabilized zirconia) balls for grinding (particle size approximately 2mm) and 200 ml of ethanol were added to a total of 100 g of the mixed powder, and the mixture was wet-mixed for 24 hours to prepare a slurry. The collected slurry was heated and stirred using a magnetic stirrer to evaporate the solvent, obtaining a dry powder. The obtained powder was sieved with a nylon sieve (150 mesh).The powder that passed the sieve was then filled into a mold (10 mm in diameter × 20 mm in length) and press molded under a pressure of about 10 MPa, followed by CIP molding under a pressure of 147 MPa. The obtained compact was degreased at 700°C for 3 hours. It was then placed in an alumina tube in a tubular furnace capable of controlling the atmosphere, and pre-sintered in an oxygen atmosphere at a heating rate of 150°C / hr up to a maximum temperature of 1380°C for 2 hours. The relative density of the pre-sintered compact was measured by the Archimedes method and found to be 98.5%. Next, the pre-sintered body was subjected to HIP treatment. The treatment conditions were Ar gas, pressure: 147 MPa, temperature: 1400°C, and treatment time: 2 hours. The HIP-treated sintered body was transparent but pale red, so it was further annealed in air at 950°C for 5 hours to remove coloration and lattice defects present inside. In this way, an apparently colorless and transparent sintered body was produced.

[0185] Examples 2 to 10 Except for the conditions shown in Table 1, ZnO was added in the same manner as in Example 1 to prepare a sintered body.

[0186] Examples 11 to 20 A sintered body was produced in the same manner as in Example 1, as shown in Table 2, except that the first additive was replaced with Ti oxide.

[0187] Examples 21 to 30 Rare earth oxide sintered bodies were produced in the same manner as in Example 1, except that the rare earth oxide was changed as shown in Table 3, and further, in Examples 21 to 25 the first additive was ZnO, and in Examples 26 to 30 the first additive was TiO2.

[0188] Examples 31 to 40 As shown in Table 4, ZnO or TiO2 was added as the first additive, and at least one of an Mg compound, a Ca compound, and an Sr compound was added as a source of the second additive. Except for this, sintered bodies were prepared in the same manner as in Example 1. In addition, MgO was used as the Mg compound, CaCO3 was used as the Ca compound, and strontium oxalate was used as the Sr compound (the same applies to the following examples).

[0189] Examples 41 to 50 As shown in Table 5, ZnO and TiO2 were co-added as the first additive, and at least one of an Mg compound, a Ca compound, and an Sr compound was added to some samples as a source of the second additive. Except for this, sintered bodies were prepared in the same manner as in Example 1.

[0190] Examples 51 to 60 As shown in Table 6, two or more kinds of rare earth oxide raw materials were used, ZnO or TiO2 was added alone as the first additive, and at least one of MgO, CaO, and SrO was added as the second additive to some samples. Except for this, sintered bodies were prepared in the same manner as in Example 1.

[0191] Example 61 Zirconia ceramics were produced according to the method of Example 1. Commercially available ZrO2 powder (purity 99.9% (total amount of ZrO2 and HfO2), average primary particle size 0.05 μm) was used as a raw material. ZnO powder (purity: 99.9%, average primary particle size 0.5 μm) was added to this powder as a first additive in the amount shown in Table 7, and 2 parts by weight of a commercially available acrylic resin binder (20% solution of acrylic resin) and 0.5 parts by weight of a dispersant were added to 100 parts by weight of these mixed powders and placed in a synthetic resin container. 1 kg of high-purity TYZ (Y-stabilized zirconia) balls for grinding (particle size about 2 mm) and 200 ml of ethanol were added to a total of 100 g of the mixed powder, and the mixture was wet-mixed for 24 hours to prepare a slurry. The collected slurry was heated and stirred using a magnetic stirrer to evaporate the solvent and obtain a dry powder. This powder was sieved using a nylon sieve (150 mesh). The powder that passed the sieve was then filled into a mold (10 mm diameter x 20 mm length) and press molded under a pressure of approximately 10 MPa, after which it was subjected to CIP molding under a pressure of 147 MPa. The obtained molded body was degreased at 600°C for 3 hours, then placed in an alumina tube in a tubular furnace capable of controlling the atmosphere, and pre-sintered in an oxygen atmosphere at a heating rate of 150°C / hr up to a maximum temperature of 1090°C for 10 hours. Next, the pre-sintered body was subjected to HIP treatment. The treatment conditions were Ar gas, pressure: 147 MPa, temperature: 1095°C, and treatment time: 2 hours. Furthermore, the HIP-treated sintered body was annealed in air at 700°C for 3 hours. The obtained sintered body was translucent and pale green in color.

[0192] Examples 62 to 80 A zirconia sintered body was produced in the same manner as in Example 61 except for the conditions shown in Tables 7 and 8.

[0193] Comparative Examples 1-2 As shown in Table 9, sintered bodies were produced in the same manner as in Example 1, except that no additives were added.

[0194] Comparative Examples 3 to 4 As shown in Table 9, sintered bodies were produced in the same manner as in Example 1, except that Zr oxide or Hf oxide was used as the sintering aid.

[0195] Comparative Examples 5 to 10 As shown in Table 9, a sintered body was produced in the same manner as in Example 1, except that the amounts of the first additive and the second additive added were outside the ranges of the present invention.

[0196] Comparative Examples 11 to 15 As shown in Table 10, additives were added within the range of the present invention, and sintered bodies were produced in the same manner as in Example 1, except that the pre-sintering conditions or HIP conditions were outside the conditions of the present invention.

[0197] Comparative Examples 16 to 25 A zirconia sintered body was produced in the same manner as in Example 61 except for the conditions shown in Table 11.

[0198] Test Example 1 The samples of each of the examples and comparative examples were evaluated for the following characteristics. The results are shown in Tables 1 to 11. Tables 1 to 11 also show the composition and the like of each sample.

[0199] (a) Analysis of added ZnO, TiO2, etc. The additives added to the material can be detected using a common analytical instrument, ICP (Inductive Coupled Plasma)-MASS, to detect the content of ZnO, TiO2, MgO, CaO, SrO, etc. in the material in weight ppm units.

[0200] (b) Average grain size of sintered body At least three arbitrary locations are observed at 200 to 1000 times magnification using a commercially available scanning electron microscope, and the particle size is measured using an image analyzer.

[0201] (c) Optical loss measurement The prepared samples are adjusted to thicknesses of 1 and 11 mm, and both sides are mirror-polished. A commercially available spectrophotometer is used to measure the transmittance of each polished sample at a wavelength of 633 nm, and the difference between the transmittance (%) of a 1 mm thick sample and the transmittance (%) of an 11 mm thick sample is the transmission loss per cm.

[0202] (d) Measurement of the amount of residual porosity in the material The prepared sample is adjusted to a thickness of 1 mm, and both sides are mirror-polished. Using a transmission microscope, photographs are taken at 100x magnification at any five locations, and the amount of residual porosity can be determined by measuring the size and number of bubbles that can be confirmed in [thickness 1 mm x observation area = observation volume]. In this invention, the term "residual porosity" refers to the total amount of pores that can be observed at 100x magnification, and bubbles that cannot be detected by this method are not counted.

[0203] (e) Extinction ratio measurement The prepared sample is adjusted to a thickness of 1 mm and both sides are mirror-polished. The sample is placed in a spectrometer and two polarizers are set on both ends of the sample. The measurement wavelength is 1000 nm, and the transmittance T H Next, the polarizing plate on one side is crossed at an angle where the transmittance is at its minimum, and the extinction value is measured as the transmittance T L Then, calculate the extinction ratio (dB value) using the following formula A. dB = 10 × log(T H / T L )...Formula A

[0204] [Table 1]

[0205] [Table 2]

[0206] [Table 3]

[0207] [Table 4]

[0208] [Table 5]

[0209] [Table 6]

[0210] [Table 7]

[0211] [Table 8]

[0212] [Table 9]

[0213] [Table 10]

[0214] [Table 11]

[0215] Example 81 A Gd2O3-based sintered body was prepared according to Example 1. Commercially available Gd2O3 powder (purity 99.9%, primary particle size 0.3μm) was mixed with 0.3 wt% ZnO powder (purity: 99.9%, average primary particle size 0.5μm), and further 2 times the amount of ethanol relative to 100 parts by weight of the raw materials, an appropriate amount of dispersant, and a commercially available acrylic resin binder (20% solution of acrylic resin) were placed in an engineering plastic, and YTZ balls were added as a grinding medium and grinding and mixing were performed for 20 hours. The obtained slurry was transferred to a beaker, and the solvent was evaporated while stirring to obtain a dry powder. The dry powder was passed through a 100 mesh sieve and molded in a mold with a diameter of 18 mm, and then CIP molded at 146 MPa. The obtained compact was degreased in air at 600°C for 3 hours, and then sintered in an oxygen atmosphere at 1050°C for 5 hours to obtain a sintered body with a relative density of 97.6%. This sintered body was subjected to HIP treatment at 1070°C for 2 hours using Ar gas as a pressure medium to obtain a transparent sintered body. The obtained sintered body was synthesized below the cubic ⇔ monoclinic phase transition temperature (1200°C) of Gd2O3, and X-ray diffraction confirmed that it had a cubic crystal structure. This material was also machined to prepare a test piece with a diameter of 12 mm and a thickness of 2 mm (the surface of the 12 mm diameter piece was mirror-polished), and the transmission spectrum was measured using a spectroscope. The absorption edge was 650 nm, and the transmittance from 700 to 1600 nm was 71.1 to 72.6%. The theoretical transmittance of this material obtained from a thin film of Gd2O3 has been reported to be 72%, so this almost reaches the theoretical transmittance. The extinction ratio of this material at 1 μm is also very high at 30 dB. The Verdet constant at a wavelength of 1064 nm is also 10 redm. -1 T -1 Although this is not a particularly large value, it was confirmed that this material is a diamagnetic material. This can also be determined from the fact that there is no wavelength dependence of the Verdet constant at wavelengths of 700 to 1600 nm. For this reason, there have been no examples of successful synthesis of transparent ceramics of Gd2O3 polycrystals, let alone single crystals, and new functions and applications as a diamagnetic Faraday element are expected. [Industrial Applicability]

[0216] In the present invention, when producing high-density and light-transmitting rare earth oxide ceramics, it has been discovered that by adding an appropriate amount of Zn and Ti oxides, which are new sintering aids that have not been reported so far, a high-density sintered body can be synthesized at a low temperature, and by optimizing the amount of addition and the synthesis conditions, it is possible to synthesize a high-quality transparent rare earth oxide ceramics. In particular, it has been thought that it is impossible to synthesize oxides of Tb, Gd, and Eu, which have low orthorhombic to cubic phase transition temperatures, but this invention has opened the door to a new technology. In particular, transparent rare earth oxide ceramics with Tb2O3 or a high TbO3 concentration have a high Verdet constant and are industrially important as promising Faraday rotators, but there was no technology to synthesize them. Such materials are expected to be industrially applied to small, high-performance isolator devices that can shut down the return waves of fiber lasers for processing. In addition, it has been confirmed that Gd2O3 can be used as a promising Faraday rotator because it can produce a transparent sintered body, the material is diamagnetic, and it has been confirmed that it has no light absorption over a wide range from visible to infrared. Due to its high density and high radiation shutdown capability, Eu2O3 is used as a window material in radiation environments. Although its uses are unknown, if the hidden potential performance of this material is discovered, it may also have industrial applications.

[0217] In addition, the present invention, which enables low-temperature synthesis, has the advantage of not only reducing the energy cost of material synthesis but also allowing the use of low-cost manufacturing equipment. It also significantly improves the grain boundary scattering problem that has been encountered in transparent rare earth oxide ceramics up to now, which will contribute greatly to improving their performance.

[0218] Thus, according to the present invention, it is possible to synthesize rare earth ceramics that are difficult to sinter at low temperatures, and it is therefore possible to provide rare earth ceramics that are dense or dense and translucent. In particular, Dy2O3, Tb2O3, etc., which are promising magneto-optical materials, have been difficult to synthesize because they undergo a cubic to orthorhombic phase transition at low temperatures, but the present invention is expected to make them possible to synthesize and improve their quality. In addition, as mentioned above, it is also possible to synthesize high-density cubic Gd2O3 ceramics, Eu2O3 ceramics, etc., and it is also possible to synthesize rare earth ceramics containing large amounts of La to Gd, so if their physical properties can be elucidated, new applications and even industrialization are expected.

Claims

1. (1) (1-1) Cubic oxide ceramics containing at least one element of the lanthanoid rare earths having atomic numbers 21 (Sc), 39 (Y), and 57 (La) to 71 (Lu), or (1-2) Monoclinic oxide ceramics containing zirconium, (2) The oxide ceramic of (1-1) or (1-2) is (a) at least one of ZnO and Ti oxide: 50 to 10,000 ppm by weight in total (however, when the element containing the atomic number 65 (Tb) is included, the content of Ti oxide is less than 1,000 ppm by weight); and (b) At least one of MgO, CaO, and SrO: 0 to 0.3% by weight in total 1. An oxide ceramic comprising:

2. 2. The oxide ceramic according to claim 1, having a relative density of 98% or more.

3. The oxide ceramic according to claim 1, having an average crystal grain size of 0.3 to 50 μm.

4. The oxide ceramic according to claim 1, wherein an optical loss for a light beam having a wavelength of 1 μm is 5% / cm or less in a thickness direction of a sample having a thickness of 2 mm of the oxide ceramic (1-1).

5. The oxide ceramic according to claim 4, wherein a sample of the oxide ceramic (1-1) having a thickness of 2 mm has an extinction ratio of 25 dB or more for a light beam having a wavelength of 1 μm in the thickness direction.

6. An optical element comprising the oxide ceramic according to claim 4.

7. The optical element according to claim 4 , which is used in an optical passive product or an optical active product.

8. 1. A method for producing rare earth oxide ceramics, comprising the steps of: (1) A process for obtaining a mixture by wet-mixing, in alcohol, a raw material including: (a) a powder of a rare earth element-containing material having an average primary particle size of 0.05 to 3 μm; and (b) a compound including at least one of Zn and Ti as a sintering aid; (2) A step of forming the mixture or a dried product thereof into a green compact; (3) pre-sintering the green compact at a temperature of 900 to 1450° C. to obtain a pre-sintered body having a relative density of 91 to 99.8%; and (4) A step of subjecting the pre-sintered body to HIP treatment at a temperature of 1000 to 1600° C. and a pressure of 98 to 392 MPa. A method for producing rare earth oxide ceramics, comprising the steps of:

9. 1. A method for producing zirconia ceramics, comprising: (1) A step of wet-mixing, in an alcohol, a raw material including (a) a monoclinic zirconia powder having an average primary particle size of 0.02 to 0.2 μm and (b) a compound including at least one of Zn and Ti as a sintering aid, to obtain a mixture; (2) forming the mixture or a dried product thereof into a green compact; and (3) A step of sintering the green compact at a temperature of 1000 to 1100° C. to obtain a sintered body having a relative density of 92 to 99.8%. A method for producing zirconia ceramics, comprising: